Dimensionally stable fast etching of glass

By developing a glass composition containing a specific oxide and producing it using a fusion drawing process, the problem of dimensional instability of existing glass substrates in high temperature processes is solved, and the effects of high dimensional stability and low compression are achieved, and the performance of liquid crystal displays is improved.

CN119528431APending Publication Date: 2025-02-28CORNING INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411717254.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2015-04-23
Filing Date
2015-10-29
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing glass substrates are prone to compression in high-temperature processes, resulting in unstable dimensions and affecting the performance of liquid crystal displays.

Method used

A new glass composition was developed, containing SiO2 68.5-72.0%, Al2O3 is greater than or equal to 13.0%, B2O3 is less than or equal to 2.5%, MgO 1.0-6.0%, CaO 4.0-8.0%, SrO is less than or equal to 4.5%, BaO is less than or equal to 4.5%, annealing point is greater than or equal to 800°C, a modulus greater than 82GPa, and an etching index is greater than or equal to 23. It is produced by a fusion drawing process, with high annealing point and high Young's modulus, which reduces compression and stress relaxation and improves dimensional stability.

Benefits of technology

High dimensional stability of glass substrates is achieved, the total pitch variability in the TFT manufacturing process is reduced, and the performance and reliability of the display are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

Substantially alkali-free glasses useful in the production of flat panel display devices (e.g., active matrix liquid crystal displays (AMLCDs)) are disclosed. The glass has high annealing temperature and etching rate. Also disclosed are methods of producing substantially alkali-free glasses using a down-draw process (e.g., a fusion process).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of a patent application with an application date of October 29, 2015, application number 201580071736.0, and name “Dimensionally stable rapid etching of glass”.

[0002] This application claims priority to U.S. Provisional Application No. 61 / 151,741, filed on April 23, 2015, and U.S. Provisional Application No. 62 / 073,938, filed on October 31, 2014, which are incorporated herein by reference in their entireties. Technical Field

[0003] Embodiments herein relate to display glass. More particularly, embodiments herein relate to display glass for active matrix liquid crystal displays. Technical Background

[0004] The production of liquid crystal displays, such as active matrix liquid crystal displays (AMLCDs), is complex and the properties of the substrate glass are important. First and foremost, the glass substrate used in the production of AMLCD devices needs to have its physical dimensions tightly controlled. Down-draw sheet drawing processes, particularly the fusion process described in U.S. Pat. Nos. 3,338,696 and 3,682,609 to Dockerty, are capable of producing glass sheets useful as substrates without the need for costly post-forming finishing operations such as lapping and polishing. Unfortunately, the fusion process places fairly severe restrictions on the properties of the glass, requiring a relatively high liquidus viscosity.

[0005] In the field of liquid crystal displays, thin film transistors (TFTs) based on polycrystalline silicon are preferred because they can transport electrons more efficiently. Silicon transistors based on polycrystalline silicon (p-Si) are characterized by higher mobility than transistors based on amorphous silicon (a-Si). This enables the manufacture of smaller and faster transistors, ultimately producing brighter and faster displays.

[0006] One of the problems with p-Si based transistors is that their manufacture requires higher process temperatures than the manufacture of a-Si transistors. These temperatures range from 450°C to 600°C, compared to the peak temperature of 350°C used when manufacturing a-Si transistors. At these temperatures, most AMLCD glass substrates undergo a process called compression. Compression, also known as thermal stability or dimensional change, is an irreversible dimensional change (contraction) of the glass substrate due to a change in the fictive temperature of the glass. "Fictive temperature" is a concept used to refer to the structural state of the glass. Glass that is cooled rapidly from a high temperature is said to have a higher fictive temperature due to the "freezing" of the higher temperature structure. Glass that is cooled more slowly or held for a period of time near its annealing point is said to have a lower fictive temperature.

[0007] The degree of compression depends on both the manufacturing process of the glass and the viscoelastic properties of the glass. In the float process, which produces a glass sheet product from glass, the glass sheet cools relatively slowly from the melt, thereby "solidifying" a relatively low temperature structure into the glass. In contrast, the fusion process causes the glass sheet to be quenched very quickly from the melt, solidifying with a relatively high temperature structure. As a result, glass produced by the float process may experience less compression than glass manufactured by the fusion process, because the driving force for compression is the difference between the fictive temperature and the process temperature experienced by the glass during compression. Therefore, it is desirable to minimize the level of compression in the glass substrate produced by the fusion process and other forming processes (e.g., float).

[0008] There are two ways to minimize compression in the glass. The first is to thermally pretreat the glass to produce a fictive temperature similar to that experienced by the glass during the p-Si TFT manufacturing process. There are some difficulties with this approach. First, the multiple heating steps used during p-Si TFT manufacturing produce slightly different fictive temperatures in the glass, and the pretreatment cannot fully compensate for the slightly different fictive temperatures. Second, the thermal stability of the glass becomes closely related to the details of p-Si TFT manufacturing, which may mean different pretreatments for different end users. Finally, pretreatment adds cost and complexity to processing.

[0009] Another approach is to slow the strain rate at processing temperatures by increasing the viscosity of the glass. This can be accomplished by raising the viscosity of the glass. For a glass, the annealing point represents the temperature corresponding to a fixed viscosity, so an increase in the annealing point is equal to an increase in viscosity at a fixed temperature. However, the challenge with this approach is to produce high annealing point glass in a cost-effective manner. The major factors affecting cost are defects and capital life. In modern melters connected to fusion draw machines, four types of defects are commonly encountered: (1) gaseous inclusions (bubbles or blisters); (2) solid inclusions from refractory materials or the inability to properly melt the batch; (3) metallic defects consisting primarily of platinum; and (4) devitrified products resulting from low liquidus viscosity or excessive devitrification at either end of the overflow trough. The composition of the glass has a disproportionate effect on the melting rate and, therefore, on the tendency of the glass to form gaseous or solid defects, and the oxidation state of the glass has an effect on the tendency to incorporate platinum defects. Devitrification of the glass on the forming mandrel or overflow trough can be best managed by selecting a composition with a high liquidus viscosity.

[0010] Capital life is primarily determined by the wear rate or deformation of the various refractory and precious metal components of the melting and forming system. In recent years, developments in refractory materials, platinum system design, and overflow tank refractoriness have provided the potential to greatly extend the usable operating life of melters adjacent to fusion draw machines. As a result, the life-limiting components of modern fusion draw melting and forming platforms are the electrodes used to heat the glass. Tin oxide electrodes corrode slowly over time, and the corrosion rate is strongly dependent on both temperature and glass composition. In order to maximize capital life, it is desirable to determine a composition that reduces the electrode corrosion rate while maintaining the defect-limiting properties described above.

[0011] As long as the compression of the glass is below a threshold level, the primary attribute that determines the suitability of the glass as a substrate is the variability or lack of variability in the overall pitch of the substrate during TFT manufacturing, which can lead to misalignment of the TFT components and result in bad pixels in the final display. This variability is primarily due to variations in glass compression, variations in the elastic deformation of the glass under stresses applied by the deposited film during TFT manufacturing, and variations in the relaxation of these same stresses during TFT manufacturing. Glass with high dimensional stability will have reduced compression variability as well as reduced stress relaxation, and glass with high Young's modulus will help reduce deformation due to film stresses. Therefore, glass with both high modulus and high dimensional stability will minimize the overall pitch variability during TFT processing, making a substrate that is advantageous for these applications.

[0012] Although total pitch variability is a key attribute of the suitability of glass composition as TFT backplane, other attributes are also quite important. After completing TFT manufacturing, panel manufacturers reduce the thickness and weight of the final display by acid etching to make the display thinner. Therefore, the glass that rapidly etches in commercially available acid compositions can be realized to make the glass thinner in a more economical manner. Similarly, glass with low density also can contribute to the required weight reduction of the final display.

[0013]

[0006] Therefore, there is a need in the art for glass compositions having high modulus and high dimensional stability while being able to be reliably reduced in thickness and having other advantageous properties and characteristics. SUMMARY OF THE INVENTION

[0014] One or more embodiments herein relate to the following glass, which comprises, based on the mole percentage of oxides: SiO2 68.5-72.0, Al2O3 greater than or equal to about 13.0, B2O3 less than or equal to about 2.5, MgO 1.0-6.0, CaO4.0-8.0, SrO less than or equal to about 4.5, BaO less than or equal to about 4.5, such that (MgO+CaO+SrO+BaO) / Al2O3 is less than or equal to about 1.6. The glass has an etching index greater than or equal to 23, an annealing point greater than or equal to about 800°C, and a modulus greater than 82 GPa.

[0015] One or more embodiments relate to the following glass, based on the molar percentage of oxides, the glass comprises: SiO2 63.0-71.0, Al2O3 13.0-14.0, B2O3>0-3.0, MgO 0.9-9.0, CaO5.25-6.5, SrO>0-6.0, BaO1.0-9.0, and the glass is substantially free of alkali metals and has an etching index>21μm / mm 3 In some embodiments, the glass comprises, based on the molar percentage of oxides: SiO2 68.0-71.0, B2O3>0-2.0, MgO 3.5-5.0, SrO>0-2.0, BaO2.5-4.5.

[0016] One or more embodiments relate to the following glass, based on the molar percentage of oxides, the glass comprises: SiO2 68.0-70.5, Al2O3 13.0-14.0, B2O3>0-3.0, MgO 0.9-9.0, CaO 5.25-11, SrO>0-6.0, BaO1.0-9.0, wherein the glass is substantially free of alkali metals and has an etching index>21μm / mm 3 In some embodiments, the glass comprises, based on the molar percentage of oxides: B2O3>0-2.0, MgO3.5-5.0, CaO 5.25-10.0, SrO>0-2.0, BaO2.5-4.5.

[0017] One or more embodiments relate to the following glass, based on the molar percentage of oxides, the glass comprises: SiO2 63.0-75.0, Al2O3 13.0-14.0, B2O3>0-2.8, MgO 0.9-9.0, CaO 5.25-11, SrO>0-6.0, BaO1.0-9.0, wherein the glass is substantially free of alkali metals and has an etching index>21μm / mm 3In some embodiments, the glass comprises, based on the molar percentage of oxides: SiO2 68.0-72.0, B2O3>0-2.0, MgO 3.5-5.0, CaO 5.25-10.0, SrO>0-2.0, BaO 2.5-4.5.

[0018] One or more embodiments herein relate to the following glass, which comprises, based on the molar percentage of oxides: SiO2 63.0-75.0, Al2O3 13.0-14.0, B2O3>0-3.0, MgO 0.9-9.0, CaO 5.25-11, SrO>0-6.0, BaO 3.0-5.4, wherein the glass is substantially free of alkali metals and has an etching index>21 μm / mm 3 In some embodiments, the glass comprises, based on the molar percentage of oxides: SiO2 68.0-72.0, B2O3>0-2.0, MgO 3.5-5.0, CaO 5.25-10.0, SrO>0-2.0, BaO 2.5-4.5.

[0019] One or more embodiments of the present invention relate to the following glass, which comprises, based on the molar percentage of oxides: SiO2 63.0-75.0, Al2O3 13.0-14.5, B2O3>0-2.0, MgO 0.9-9.0, CaO 5.0-6.5, SrO>0-6.0, BaO 1.0-9.0, wherein the glass is substantially free of alkali metals, (MgO+CaO+SrO+BaO) / Al2O3 is 1.1-1.6, and the etching index is>21μm / mm 3 In some embodiments, the glass comprises, based on the molar percentage of oxides: SiO2 68.0-72.0, MgO 3.5-5.0, CaO 5.25-6.5, SrO>0-2.0, BaO 2.5-4.5.

[0020] One or more embodiments relate to the following glass, based on the molar percentage of oxides, the glass comprises: SiO2 63.0-71.0, Al2O3 13.0-14.0, B2O3>0-2.0, MgO 0.9-9.0, CaO5.25-6.5, SrO>0-6.0, BaO1.0-9.0, wherein the glass is substantially free of alkali metals and has an etching index>21μm / mm 3 In some embodiments, the glass comprises, based on the molar percentage of oxides: SiO2 68.0-71.0, MgO 3.5-5.0, SrO>0-2.0, BaO 2.5-4.5.

[0021] One or more embodiments relate to the following glass, based on the molar percentage of oxides, the glass comprises: SiO2 63.0-71.0, Al2O3 13.0-14.0, B2O3>0-2.0, MgO 0.9-9.0, CaO 5.0-6.5, SrO>0-6.0, BaO3.5-4.0, wherein the glass is substantially free of alkali metals and has an etching index>21μm / mm 3 In some embodiments, the glass comprises, based on the molar percentage of oxides: SiO2 68.0-71.0, MgO 3.5-5.0, SrO>0-2.0.

[0022] One or more embodiments relate to a glass comprising, based on the molar percentage of oxides, SiO2 63.0-71.0, Al2O3 13.0-14.0, B2O3>0-2.0, MgO 0.9-9.0, CaO 5.0-6.5, SrO>0-6.0, BaO1.0-9.0, the sum of CaO and BaO>8.6, wherein the glass is substantially free of alkali metals and has an etching index>21 μm / mm 3 In some embodiments, the glass comprises, based on the molar percentage of oxides: SiO2 68.0-71.0, MgO 3.5-5.0, SrO>0-2.0, BaO 2.5-4.5.

[0023] Other embodiments herein relate to glasses having an annealing temperature of about 785° C. or greater; a density of about 2.65 g / cc or less; and a T 200P Less than or equal to about 1750°C; T 35kP Less than or equal to about 1340°C; Young's modulus greater than or equal to about 82 GPa; and etching index greater than or equal to about 21 μm / mm 3 , the etching index is defined by the following equation: -54.6147+(2.50004)*(Al2O3)+(1.3134)*(B2O3)+(1.84106)*(MgO)+(3.01223)*(CaO)+(3.7248)*(SrO)+(4.13149)*(BaO), wherein the glass is substantially free of alkali metals. In some embodiments, the glass has one or more of the following properties: annealing temperature greater than or equal to about 800°C; density less than or equal to about 2.61 g / cc; T 200P Less than or equal to about 1700°C; T 35kP Less than or equal to about 1310°C; and / or an etching index greater than or equal to about 21 μm / mm 3In various embodiments, the glass comprises one or more of: SiO2 in the range of 68.1-72.3 as a mole percent of oxide; Al2O3 in the range of 11.0-14.0 as a mole percent of oxide; B2O3 in the range of >0-3.0 as a mole percent of oxide; MgO in the range of 1.0-7.2 as a mole percent of oxide; MgO in the range of 3.1-5.8 as a mole percent of oxide; CaO in the range of 4.1-10.0 as a mole percent of oxide; CaO in the range of 4.5-7.4 as a mole percent of oxide; SrO in the range of >0-4.2 as a mole percent of oxide; SrO in the range of >0-2.0 as a mole percent of oxide; BaO in the range of 1.2-4.4 as a mole percent of oxide; and / or BaO in the range of 2.6-4.4 as a mole percent of oxide. In some embodiments, the glass comprises, based on the molar percentage of oxides: SiO2 68.0-72.0, B2O3 0.1-3.0, and CaO 5.0-6.5. In one or more embodiments, the glass comprises, based on the molar percentage of oxides: Al2O3 13.0-14.0, B2O3 0.1-3.0, and CaO 5.25-6.0.

[0024] Some embodiments herein relate to glasses that are substantially free of alkali metals. The glass comprises, in terms of mole % of oxides: SiO2 69.76-71.62, Al2O3 11.03-13.57, B2O3 0-2.99, MgO 3.15-5.84, CaO 4.55-7.35, SrO 0.2-1.99, BaO 2.61-4.41, and ZnO 0-1.0, wherein the ratio (MgO+CaO+SrO+BaO) / Al2O3 is about 1.0 to 1.6, and the ratio MgO / (MgO+CaO+SrO+BaO) is about 0.22 to 0.37.

[0025] One or more embodiments herein relate to a substantially alkali-free glass comprising, in terms of mole % of oxides, SiO2 68.14-72.29, Al2O3 11.03-14.18, B2O3 0-2.99, MgO 1.09-7.2, CaO 4.12-9.97, SrO 0.2-4.15, BaO 1.26-4.41, and ZnO 0-1.0, wherein the ratio (MgO+CaO+SrO+BaO) / Al2O3 is approximately 1.0 to 1.6, and the ratio MgO / (MgO+CaO+SrO+BaO) is approximately 0.22 to 0.37.

[0026] Some embodiments herein relate to glasses that are substantially free of alkali metals. The glasses have the following ratios: (MgO+CaO+SrO+BaO) / Al2O3 is about 1.0 to 1.6, MgO / (MgO+CaO+SrO+BaO) is about 0.22 to 0.37, T(annealed)>785°C, density<2.65 g / cc, T(200P)<1750°C, T(35kP)<1340°C, Young's modulus>82 GPa, and etching index>21 μm / mm 3 .

[0027] Other embodiments herein relate to substantially alkali-free glasses, wherein (MgO+CaO+SrO+BaO) / Al2O3 is about 1.0 to 1.6, the ratio MgO / (MgO+CaO+SrO+BaO) is about 0.22 to 0.37, and the etching index is >21 μm / mm 3 .

[0028] In one or more embodiments, the substantially alkali-free glass has a (MgO+CaO+SrO+BaO) / Al2O3 of about 1.0 to 1.6, a ratio MgO / (MgO+CaO+SrO+BaO) of about 0.22 to 0.37, and a liquidus viscosity >150 kP.

[0029] Some embodiments herein relate to glasses that are substantially free of alkali metals, wherein (MgO+CaO+SrO+BaO) / Al2O3 is about 1.0 to 1.6, and an etching index is greater than or equal to 21 μm / mm 3 , T(annealing)>800℃ and Young's modulus>82GPa.

[0030] Other embodiments herein relate to aluminosilicate glass articles that are substantially free of alkali metals. The glass articles have an annealing temperature greater than or equal to about 795° C.; a density less than or equal to about 2.63 g / cc; and a T 200P Less than or equal to about 1730°C; T 35kP Less than or equal to about 1320°C; Young's modulus greater than or equal to 81.5 GPa; and etching index greater than or equal to about 23 μm / mm 3 .

[0031] Other embodiments herein relate to aluminosilicate glass articles that are substantially free of alkali metals. The article has an annealing temperature greater than or equal to about 800° C.; a density less than or equal to about 2.61 g / cc; T 200P Less than or equal to about 1710°C; T 35kP Less than or equal to about 1310°C; Young's modulus greater than or equal to 81.2 GPa; and etching index greater than or equal to about 23 μm / mm 3 .

[0032] Other embodiments herein are directed to objects comprising glass produced by a down-drawn sheet manufacturing process.Other embodiments are directed to glass produced by a fusion process or variations thereof. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate several embodiments described below.

[0034] Figure 1 A schematic diagram showing a forming mandrel used to make precision sheet in a fusion draw process;

[0035] Figure 2 show Figure 1 A cross-sectional view of the forming mandrel along position 6; and

[0036] Figure 3 Eagle showing 0.7mm thickness Transmission spectrum of an amorphous thin-film transistor substrate and blackbody spectra at 1200°C and 1140°C. DETAILED DESCRIPTION

[0037] Alkali-free glasses and methods of making the same are described herein, which have a high annealing point and a high Young's modulus, so that the glass has excellent dimensional stability (i.e., low compression) during TFT manufacturing, reducing variability during the TFT process. Glasses with high annealing points can prevent panel deformation due to compression / contraction during thermal processing after glass manufacturing. In addition, some embodiments herein have high etch rates, allowing for economical thinning of the backplane, and have unusually high liquidus viscosities, thereby reducing or eliminating the possibility of devitrification on colder forming mandrels. As a result of the specific details of its composition, the exemplary glass melts to high quality, has very low levels of gaseous inclusions, and minimizes corrosion of precious metals, refractory materials, and tin oxide electrode materials.

[0038] In one embodiment, the substantially alkali-free glass may have a high annealing point. In some embodiments, the annealing point is greater than about 785° C., 790° C., 795° C., or 800° C. Without wishing to be bound by any particular theory of operation, it is believed that such a high annealing point results in a low relaxation rate for the exemplary glass to be used as a backplane substrate in a low temperature polysilicon process, resulting in a relatively small amount of compression.

[0039] In another embodiment, the exemplary glass has a viscosity of about 35,000 poise at a temperature (T 35k) is less than or equal to about 1340° C., 1335° C., 1330° C., 1325° C., 1320° C., 1315° C., 1310° C., 1300° C., or 1290° C. In a specific embodiment, the glass has a viscosity of about 35,000 poise (T 35k ) is less than about 1310° C. In other embodiments, the exemplary glass has a viscosity of about 35,000 poise at a temperature (T 35k ) is less than about 1340°C, 1335°C, 1330°C, 1325°C, 1320°C, 1315°C, 1310°C, 1300°C, or 1290°C. In various embodiments, the glass article has a T 35k About 1275°C to about 1340°C, or about 1280°C to about 1315°C.

[0040] The liquidus temperature of glass (T 液相线 ) is the temperature at which a crystalline phase can coexist in equilibrium with the glass, but above which it cannot coexist. In various embodiments, the T of the glass article 液相线 In another embodiment, the viscosity corresponding to the liquidus temperature of the glass is greater than or equal to about 150,000 poise. In some embodiments, the viscosity corresponding to the liquidus temperature of the glass is greater than or equal to about 175,000 poise, 200,000 poise, 225,000 poise, or 250,000 poise.

[0041] In another embodiment, the exemplary glass may provide a T 35k –T 液相线 >0.25T 35k –225°C. This ensures that the tendency to devitrification on the forming mandrel of the fusion process is minimized.

[0042] In one or more embodiments, the substantially alkali-free glass comprises the following, in mole percent of oxides:

[0043] SiO2 60-80

[0044] Al2O3 5-20

[0045] B2O3 0-10

[0046] MgO 0-20

[0047] CaO 0-20

[0048] SrO 0-20

[0049] BaO 0-20

[0050] ZnO 0-20

[0051] Wherein, Al2O3, MgO, CaO, SrO, and BaO represent the molar percentages of the oxide components, respectively.

[0052] In some embodiments, the substantially alkali-free glass comprises the following, in mole percent of oxides:

[0053] SiO2 65-75

[0054] Al2O3 10-15

[0055] B2O3 0-3.5

[0056] MgO 0-7.5

[0057] CaO 4-10

[0058] SrO 0-5

[0059] BaO 1-5

[0060] ZnO 0-5

[0061] in

[0062] 1.0≤(MgO+CaO+SrO+BaO) / Al2O3<2 and 0 <MgO / (MgO+Ca+SrO+BaO)<0.5。

[0063] In certain embodiments, the substantially alkali-free glass comprises the following, in mole percent of oxides:

[0064] SiO2 67-72

[0065] Al2O3 11-14

[0066] B2O3 0-3

[0067] MgO 3-6

[0068] CaO 4-8

[0069] SrO 0-2

[0070] BaO 2-5

[0071] ZnO 0-1

[0072] in

[0073] 1.0≤(MgO+CaO+SrO+BaO) / Al2O3<1.6 and 0.20 <MgO / (MgO+Ca+SrO+BaO)<0.40。

[0074] In one embodiment, the glass includes a chemical fining agent. Such fining agents include, but are not limited to, SnO2, As2O3, Sb2O3, F, Cl and Br, and wherein the concentration of the chemical fining agent is maintained at a level of less than or equal to 0.5 mol%. In some embodiments, the chemical fining agent includes one or more of the following: SnO2, As2O3, Sb2O3, F, Cl or Br, and its concentration is less than or equal to about 0.5 mol%, 0.45 mol%, 0.35 mol%, 0.3 mol%, or 0.2 mol%. The chemical fining agent may also include CeO2, Fe2O3 and other transition metal oxides, such as MnO2. These oxides may introduce color to the glass through their visible light absorption in the final valence band state in the glass, so their concentration may be at a level of less than or equal to 0.2 mol%. In one or more embodiments, the glass composition includes one or more oxides of transition metals, and its concentration is less than or equal to about 0.2 mol%, 0.15 mol%, 0.1 mol%, or 0.05 mol%. In some embodiments, the glass composition includes about 0.01 mol% to about 0.4 mol% of any one or combination of SnO2, As2O3, Sb2O3, F, Cl, and / or Br. In a specific embodiment, the glass composition includes about 0.005 mol% to about 0.2 mol% of any one or combination of Fe2O3, CeO2, and / or MnO2. In some embodiments, As2O3 and Sb2O3 comprise less than or equal to about 0.005 mol% of the glass composition.

[0075] In one embodiment, the exemplary glass is made into sheets by a fusion process. The fusion drawing process can produce a pristine, flame-polished glass surface that reduces surface-mediated deformation for high-resolution TFT backplanes and color filters. Figure 1 is a schematic diagram of a forming mandrel or isopipe in an unrestrained fusion draw process. Figure 2 yes Figure 1 Schematic diagram of a cross-section of an overflow trough near position 6 in FIG. Glass is introduced from inlet 1 and flows along the bottom of the trough 4 formed by the weir wall 9 to the compression end 2. The glass overflows the weir wall 9 on either side of the overflow trough (see FIG. Figure 2 ), and the two glass streams meet or fuse at the root 10. Edge directors 3 at either end of the isopipe serve to cool the glass and produce a thicker strip (called a bead) at the edge. The bead is pulled downward by pulling rolls, thereby forming a sheet at a high viscosity. By adjusting the rate at which the sheet is pulled from the isopipe, a fusion draw process can be used to produce a very wide range of thicknesses at a fixed melt rate.

[0076] A down-draw sheet drawing process may be employed herein, specifically, the fusion process described in U.S. Pat. Nos. 3,338,696 and 3,682,609 (both to Dockerty), which are incorporated herein by reference. Without wishing to be bound by any particular theory of operation, it is believed that the fusion process can produce a glass substrate that does not require polishing. Existing glass substrate polishing is capable of producing a glass substrate having an average surface roughness greater than about 0.5 nm (Ra), as measured by atomic force microscopy. The glass substrate produced by the fusion process has an average surface roughness of less than 0.5 nm as measured by atomic force microscopy. The substrate also has an average internal stress of less than or equal to 150 psi as measured by optical delay. Of course, the claims appended hereto should not be limited to the fusion process, as the embodiments described herein are equally applicable to other forming processes, such as, but not limited to, float forming processes.

[0077] In one embodiment, the exemplary glasses are formed into sheet form using a fusion process. Although the exemplary glasses are compatible with fusion processes, they can also be formed into sheets or other articles by different manufacturing methods. Such processes include slot drawing processes, float processes, rolling processes, and other sheet forming processes known to those skilled in the art.

[0078] Relative to these alternative methods for producing glass sheets, the fusion method described above is capable of producing very thin, very flat, very uniform sheets with pristine surfaces. Slit drawing can also produce pristine surfaces, but the dimensional uniformity and surface quality of slot-drawn glass are generally inferior to fusion-drawn glass because of changes in pore shape over time, the accumulation of volatile impurities at the pore-glass interface, and the challenges of forming pores to deliver truly flat glass. The float process is capable of delivering very large, uniform sheets, but the surface is significantly damaged because one side is in contact with the float bath and the other side is exposed to condensation products from the float bath. This means that float glass must be polished in order to be used in high-performance display applications.

[0079] The float process may involve rapid cooling of the glass from a high temperature, which results in a high fictive temperature T f The fictive temperature can be thought of as representing the difference between the structural state of the glass and the state it would assume if it were fully relaxed at the temperature of interest. g Reheat to processing temperature T p Make T p <T g ≤T f , which may be affected by the viscosity of the glass. p <T f , the structural state of the glass is at T p is unbalanced, so the glass will spontaneously relax to pThe rate of this relaxation is related to the glass at T p The effective viscosity at T is amplified inversely, so that high viscosity leads to a slow relaxation rate, while low viscosity leads to a fast relaxation rate. The effective viscosity varies inversely with the fictive temperature of the glass, so that a low fictive temperature leads to a high viscosity, while a high fictive temperature leads to a relatively low viscosity. Therefore, T p The relaxation rate at T is directly proportional to the fictive temperature of the glass. p When the glass is heated again under low temperature, the method of introducing a high fictive temperature results in a relatively high relaxation rate.

[0080] Lower T p One way to reduce the relaxation rate is to increase the viscosity of the glass at that temperature. The annealing point of a glass indicates that the glass has 10 13.2 As the temperature decreases below the annealing point, the viscosity of the supercooled melt increases. g At a fixed temperature, the viscosity of the glass with a higher annealing point is higher than that of the glass with a lower annealing point. Therefore, increasing the annealing point can increase the viscosity of the substrate glass at T p Generally speaking, the composition changes necessary to increase the annealing point also increase the viscosity at all other temperatures. In a non-limiting embodiment, the fictive temperature of the glass produced by the fusion process corresponds to about 10 11 -10 12 The viscosity of the glass is increased, and thus the annealing point of the glass is increased for a fusion-compatible glass, and usually also its fictive temperature. For a given glass, regardless of the forming process, a higher fictive temperature results in a temperature below T g The lower the viscosity at the temperature, the higher the fictive temperature, so increasing the fictive temperature has the opposite effect of increasing the viscosity, which would otherwise be achieved by increasing the annealing point. p Significant changes in the relaxation rate at low temperatures generally necessitate a large change in the annealing point. One aspect of the exemplary glass is that its annealing point is greater than or equal to about 785°C, or 790°C, or 795°C, or 800°C, or 805°C, or 810°C, or 815°C, or is in the range of about 796.1°C to about 818.3°C. Without wishing to be bound by any particular theory of operation, it is believed that such high annealing points result in an acceptably low rate of thermal relaxation during low temperature TFT processing (e.g., a typical low temperature polysilicon rapid thermal annealing cycle).

[0081] In addition to its effect on the fictive temperature, an increase in the annealing point also increases the temperature of the entire melting and forming system, especially the temperature of the isopipe. Glass and Lotus TMThe annealing points of the glasses (Corning Incorporated, Corning, NY) differ by about 50°C, and the temperatures at which they are transferred to the isopipe also differ by about 50°C. When held above about 1310°C for extended periods of time, the zirconium refractory material forming the isopipe exhibits thermal creep, which is accelerated by the weight of the isopipe plus the weight of the glass on the isopipe. A second aspect of the exemplary glasses is that their transfer temperatures are less than or equal to about 1350°C, or 1345°C, or 1340°C, or 1335°C, or 1330°C, or 1325°C, or 1320°C, or 1315°C, or 1310°C. Such transfer temperatures may allow for extended manufacturing activities without the need to replace the isopipe, or may allow for extended time between replacements of the isopipe.

[0082] In manufacturing trials of glasses with high annealing points and transfer temperatures below 1350°C and below 1310°C, it was found that they showed a greater tendency to devitrify at the root of the isopipe, especially at the edge directors relative to glasses with lower annealing points. Careful measurement of the temperature profile on the isopipe showed that the edge director temperature relative to the central root temperature was much lower than expected and it is believed that this is due to radiative heat losses. The edge director temperature is usually maintained below the central root temperature to ensure that the glass is viscous enough when it leaves the root so that the sheet between the edge directors is under tension and thus maintains a flat shape. Since the edge directors are located at either end of the isopipe, it is difficult to heat the edge directors and the temperature difference between the center of the root and the edge directors can differ by more than or equal to 50°.

[0083] While not wishing to be bound by theory, it is believed that the increased tendency for devitrification to occur during the fusion process can be understood as a function of the radiative heat loss of the glass versus temperature. Fusion is essentially an isothermal process, so that the glass exits the inlet at a certain viscosity and exits the root at a much higher viscosity, but the actual value used for the viscosity is not strongly dependent on the properties of the glass or the temperature of the process. Thus, glasses with higher annealing points generally require much higher isopipe temperatures than glasses with lower annealing points to match the transfer and exit viscosities. For example, Figure 3 The corresponding temperatures are 1140℃ and 1200℃ (approximately Eagle Glass and Lotus TM Glass at the root of the overflow trough ( Figure 2The blackbody spectrum of borosilicate glass at a temperature of 10) in the near infrared (Fig. 10). The vertical straight line at about 2.5 microns corresponds approximately to the start of the infrared cutoff, through which the optical absorption in borosilicate glass rises very steeply to a higher, almost constant value in the near infrared region. At wavelengths shorter than the cutoff wavelength, the glass is transparently sensitive to wavelengths between 300-400 nanometers in the UV cutoff. Between about 300nm and about 2.5um, the 1200°C blackbody has greater absolute energy than the 1140°C blackbody, and accounts for a greater fraction of its total energy. Because the glass is transparently sensitive throughout this wavelength range, the radiative heat loss from the glass at 1200°C is much greater than the radiative heat loss from the glass at 1140°C.

[0084] Again, without wishing to be bound by any particular theory of operation, it is believed that because radiative heat losses increase with temperature, and because high annealing point glass is generally formed at higher temperatures than lower annealing point glass, the temperature difference between the central root and the edge director generally increases with the annealing point of the glass. This may have a direct relationship to the tendency of the glass to form devitrification products on the isopipe or edge director.

[0085] The liquidus temperature of a glass is defined as the highest temperature at which a crystalline phase will appear if the glass is held at that temperature indefinitely. The liquidus viscosity is the viscosity of the glass at the liquidus temperature. To avoid devitrification on the isopipe altogether, it may be useful to have a liquidus viscosity high enough to ensure that the glass is no longer at or near the liquidus temperature on the isopipe refractory material or edge director material.

[0086] In practice, few alkali-free glasses have the desired liquidus viscosity. Experience with glass) has shown that the edge director can be continuously maintained at a temperature as high as 60° below the liquidus temperature of some alkali-free glasses. While it is understood that glasses with higher annealing points will require higher forming temperatures, it was not expected that the edge director would be so much cooler relative to the central root temperature. A useful metric to keep track of this effect is the transfer temperature to the isopipe compared to the liquidus temperature of the glass, T 液相 In the fusion process, it is usually desired to be about 35000 poise (T 35k ) transfer glass. For a specific transfer temperature, T 35k -T 液相线 As large as possible may be useful, but for amorphous silicon substrates (e.g., Eagle glass), it is found that if T 35k -T 液相线 Greater than or equal to about 80° can be used for extended manufacturing activities. As the temperature increases, T 35k -T液相线 must also increase, so that for T close to 1300°C 35k , so that T 35k -T 液相线 Temperatures equal to or greater than about 100°C may be useful. 35k -T 液相线 The minimum usable value of varies approximately linearly with temperature from about 1200°C to about 1320°C, which can be expressed as the following equation (1):

[0087] Minimum T 35k -T 液相线 =0.25T 35k –225, (1)

[0088] Wherein, all temperatures are in °C. Thus, T of one or more embodiments of the exemplary glass 35k –T 液相线 >0.25T 35k –225℃.

[0089] In addition, the forming process may require the glass to have a high liquidus viscosity. This is necessary to avoid devitrification products at the interface with the glass and to minimize visible devitrification products in the final glass. Therefore, for a given glass compatible with fusion having a specific sheet size and thickness, adjusting the process to produce a wider sheet or a thicker sheet generally results in lower temperatures at either end of the isopipe. Some embodiments have a higher liquidus viscosity, thereby providing greater flexibility for manufacturing by the fusion process. In some embodiments, the liquidus viscosity is greater than or equal to about 150 kP.

[0090] In testing the relationship between liquidus viscosity and subsequent devitrification tendency of the fusion process, the inventors surprisingly observed that high transfer temperatures (such as those of the exemplary glasses) generally require higher liquidus viscosities for long-term production than typical AMLCD substrate compositions with lower annealing points. Although not wishing to be bound by theory, it is believed that this results from the acceleration of crystal growth as temperature increases. Fusion is essentially an isovistoric process, so a more viscous glass can be formed by fusion at a higher temperature than a less viscous glass at some fixed temperature. Although at lower temperatures, a certain degree of undercooling (cooling to below the liquidus temperature) can be allowed to continue for an extended period of time in the glass, the crystal growth rate increases with temperature, so that a more viscous glass grows a considerable amount of unacceptable devitrification products in a shorter period of time than a less viscous glass. Depending on where it is formed, the devitrification products can damage the forming stability and introduce visible defects into the final glass.

[0091] In order to be formed by a fusion process, one or more embodiments of the glass composition have a liquidus viscosity greater than or equal to about 150,000 poise, or 175,000 poise, or 200,000 poise. A surprising result is that in the entire range of exemplary glasses, sufficiently low liquidus temperatures and sufficiently high viscosities can be achieved so that the liquidus viscosities of the glasses are unusually high compared to other compositions.

[0092] In the glass compositions described herein, SiO2 acts as a basic glass former. In certain embodiments, in order to provide a glass having a density and chemical durability suitable for flat panel display glass (e.g., AMLCD glass), and a liquidus temperature (liquidus viscosity) that allows the glass to be formed by a down-draw process (e.g., a fusion process), the SiO2 concentration may be greater than 60 mol%. Generally speaking, for the upper limit, the SiO2 concentration may be less than or equal to about 80 mol% to achieve melting of the batch material using conventional high volume melting techniques (e.g., Joule melting in a refractory furnace). As the SiO2 concentration increases, the 200 poise temperature (melting temperature) generally increases. In various applications, the SiO2 concentration is adjusted so that the melting temperature of the glass composition is less than or equal to 1750°C. In some embodiments, the SiO2 concentration is in the range of about 63.0-75.0 mol%, or about 63.0-71.0 mol%, or about 65.0-73 mol%, or about 67-72 mol%, or about 68.0-72.0 mol%, or about 68.0-71.0 mol%, or about 68.0-70.5 mol%, or about 68.1-72.3 mol%, or about 68.5-72.0 mol%, or about 68.95-71.12 mol%, or about 69.7-71.7 mol%.

[0093] Al2O3 is another glass former used to make the glasses described herein. Al2O3 concentrations greater than or equal to 10 mol% provide glasses having low liquidus temperatures and high viscosities, resulting in high liquidus viscosities. The use of at least 10 mol% Al2O3 also improves the annealing point and modulus of the glass. To this end, the ratio (MgO+CaO+SrO+BaO) / Al2O3 is greater than or equal to 1.0, and the Al2O3 concentration can be less than about 15 mol%. In some embodiments, the Al2O3 concentration is in the range of about 11.01-14.0 mol%, or about 11.0-13.6 mol%, or about 13.0-14.5 mol%, or about 13.0-14.0 mol%, or about 13.0-14.18 mol%. In some embodiments, the Al2O3 concentration is greater than or equal to about 9.5 mol%, 10.0 mol%, 10.5 mol%, 11.0 mol%, 11.5 mol%, 12.0 mol%, 12.5 mol%, or 13.0 mol%, while maintaining the ratio (MgO+CaO+SrO+BaO) / Al2O3 greater than or equal to about 1.0.

[0094] Some embodiments herein have a modulus greater than about 81 GPa, or 81.5 GPa, or 82 GPa, or 82.5 GPa, or 83 GPa, or 83.5 GPa, or 84 GPa, or 84.5 GPa, or 85 GPa. In various embodiments, the aluminosilicate glass article has a Young's modulus of about 81-88 GPa, about 81.5-85 GPa, or about 82-84.5 GPa.

[0095] Some embodiments of the aluminosilicate glass articles have a density of less than about 2.7 g / cc, or about 2.65 g / cc, or about 2.61 g / cc, or about 2.6 g / cc, or about 2.55 g / cc. In various embodiments, the density is about 2.55-2.65 g / cc, or about 2.57-2.626 g / cc.

[0096] B2O3 is both a glass former and a flux, aiding in melting and lowering the melting temperature. It has an effect on both the liquidus temperature and the viscosity. Increasing B2O3 can be used to increase the liquidus viscosity of the glass. To achieve these effects, the B2O3 concentration of the glass composition of one or more embodiments may be greater than or equal to 0.1 mol%. As described above with respect to SiO2, glass durability is very important for LCD applications. Durability can be slightly controlled by increasing the concentration of alkaline earth oxides, and significantly reduced by increasing the B2O3 content. The annealing point decreases as B2O3 increases, so it may be useful to keep the B2O3 content low relative to its typical concentration in an amorphous silicon substrate. Thus, in some embodiments, the glass composition has a B2O3 concentration in the range of about 0.0-3.0 mol%, or greater than 0 to about 3.0 mol%, or about 0.0-2.8 mol%, or greater than 0 to about 2.8 mol%, or 0.0 to about 2.5 mol%, or greater than 0 to 2.5 mol%, or about 0.0-2.0 mol%, or greater than 0 to about 2.0 mol%, or about 0.1-3.0 mol%, or about 0.75-2.13 mol%.

[0097] The concentrations of Al2O3 and B2O3 can be selected in pairs to increase the annealing point, increase modulus, improve durability, reduce density, and reduce the coefficient of thermal expansion (CTE) while maintaining the melting and forming properties of the glass.

[0098] For example, an increase in B2O3 and a corresponding decrease in Al2O3 can help achieve lower density and CTE, while an increase in Al2O3 and a corresponding decrease in B2O3 can help increase annealing point, modulus, and durability, provided that the increase in Al2O3 does not reduce the (MgO+CaO+SrO+BaO) / Al2O3 ratio to below about 1.0. For a (MgO+CaO+SrO+BaO) / Al2O3 ratio below about 1.0, it may be difficult or impossible to remove gaseous inclusions from the glass due to late stage melting of the silica raw materials. In addition, when (MgO+CaO+SrO+BaO) / Al2O3≤1.05, aluminosilicate crystalline mullite may appear as a liquidus phase. Once mullite is present as a liquidus phase, the composition sensitivity of the liquidus is significantly increased, and the mullite devitrification product grows very rapidly and is also very difficult to remove once established. Thus, in some embodiments, the glass composition has (MgO+CaO+SrO+BaO) / Al2O3≥1.0 (or greater than or equal to about 1.0). In various embodiments, the glass has (MgO+CaO+SrO+BaO) / Al2O3≥1.05 (or greater than or equal to about 1.05), or is about 1-1.17.

[0099] In one or more embodiments, the coefficient of thermal expansion (CTE) (22-300° C.) of glass for AMLCD applications is about 28 x 10 -7 / ℃ to about 42x 10 -7 / °C, or about 30 x 10 -7 / ℃ to about 40x10 -7 / °C, or about 32 x 10 -7 / ℃ to about 38x 10 -7 / ℃.

[0100] In addition to the glass formers (SiO2, Al2O3 and B2O3), the glasses described herein also contain alkaline earth oxides. In one embodiment, at least three alkaline earth oxides are glass components, such as MgO, CaO and BaO, and optionally SrO. Alkaline earth oxides provide various properties important for melting, clarification, forming and final application to the glass. Therefore, in order to improve the glass performance in these aspects, in one embodiment, the ratio of (MgO + CaO + SrO + BaO) / Al2O3 is greater than or equal to about 1.0. As this ratio increases, the viscosity tends to increase more strongly than the liquidus temperature, so it is important to obtain a suitable high value of T 35k -T 液相线 It is getting more and more difficult. Therefore, in another embodiment, the ratio (MgO + CaO + SrO + BaO) / Al2O3 is less than or equal to about 2. In some embodiments, the ratio (MgO + CaO + SrO + BaO) / Al2O3 is about 1-1.2, or about 1-1.16, or about 1.1-1.6. In a specific embodiment, the ratio (MgO + CaO + SrO + BaO) / Al2O3 is less than about 1.7, or 1.6 or 1.5.

[0101] For certain embodiments herein, the alkaline earth oxides may be considered to be effectively single constituents. This is because their effects on viscoelastic properties, liquidus temperature, and the relationship between liquidus phases are more similar to each other than the glass-forming oxides SiO2, Al2O3, and B2O3. However, the alkaline earth oxides CaO, SrO, and BaO may form feldspar minerals, particularly calcium feldspar (CaAl2Si2O8) and barium feldspar (BaAl2Si2O8), and their strontium-containing solid solutions, but MgO does not participate in these crystals to a significant extent. Therefore, when the feldspar crystals are already in the liquidus phase, the super addition of MgO may have the effect of stabilizing the liquid relative to the crystals, thereby lowering the liquidus temperature. At the same time, the viscosity curve generally becomes steeper, lowering the melting temperature but having little or no effect on the low temperature viscosity.

[0102] The inventors have discovered that adding small amounts of MgO benefits melting by lowering the melting temperature, benefits forming by lowering the liquidus temperature and increasing the liquidus viscosity, while maintaining a high annealing point and thus low compression. In various embodiments, the glass composition includes MgO in an amount of about 0.9-9 mol%, or about 1.0-7.2 mol%, or about 1.0-6.0 mol%, or about 2.1-5.68 mol%, or about 3.1-5.9 mol%, or about 3.5-5.0 mol%.

[0103] The inventors surprisingly found that having a suitable high T 35k -T 液相线 For glasses with high MgO values, the ratio of MgO to other alkaline earth materials (MgO / (MgO+CaO+SrO+BaO)) falls within a narrow range. As mentioned above, the addition of MgO destabilizes the feldspar minerals, thus stabilizing the liquid and lowering the liquidus temperature. However, once MgO reaches a certain level, the mullite Al6Si2O 13 The MgO concentration may be stabilized, thereby increasing the liquidus temperature and decreasing the liquidus viscosity. In addition, higher MgO concentrations tend to decrease the viscosity of the liquid, so even if the liquidus viscosity remains constant by adding MgO, the final situation is still that the liquidus viscosity decreases. Therefore, in another embodiment, 0.20≤MgO / (MgO+CaO+SrO+BaO)≤0.40, or in some embodiments, 0.22≤MgO / (MgO+CaO+SrO+BaO)≤0.37. Within these ranges, MgO can be varied relative to the glass formers and other alkaline earth oxides to maximize T consistent with obtaining other desired properties. 35k -T 液相线 value.

[0104] Without wishing to be bound by any particular theory of operation, it is believed that the presence of calcium oxide in the glass composition can produce a low liquidus temperature (high liquidus viscosity), a high annealing point and modulus, and the most desirable CTE range for flat panel applications, particularly AMLCD applications. It also has a positive effect on chemical durability and is a relatively inexpensive batch material compared to other alkaline earth oxides. However, at high concentrations, CaO increases density and CTE. In addition, at sufficiently low SiO2 concentrations, CaO can stabilize anorthite, thereby reducing liquidus viscosity. Therefore, in one or more embodiments, the CaO concentration can be greater than or equal to 4 mole percent or 4.0 mole percent. In various embodiments, the CaO concentration of the glass composition is in the range of about 4.0-8.0 mol%, or about 4.1-10.0 (or 10.0) mol%, or about 4.12-7.45 mol%, or about 4.5-7.4 mol%, or about 5.0-6.5 mol%, or about 5.25-11 (or 11.0) mol%, or about 5.25-10 (or 10.0) mol%, or about 5.25-6.5 mol%, or about 5.25-6.0 mol%.

[0105] Both SrO and BaO can contribute to low liquidus temperature (high liquidus viscosity), so the glasses described herein will generally contain at least these two oxides. However, the selection and concentration of these oxides are selected to avoid increases in CTE and density and decreases in modulus and annealing point. The relative proportions of SrO and BaO can be balanced to obtain a combination of suitable physical properties and liquidus viscosity so that the glass can be formed by a down-draw process. In various embodiments, the glass contains SrO in the range of about 0-6.0 mol%, or greater than 0 to about 6.0 mol%, or about 0 to 4.5 mol%, to 4.2 mol%, or to 2.0 mol%, or greater than 0 to about 4.5 mol%, to about 4.2 mol%, or to 2.0 mol%, or about 0.45 mol% to about 4.15 mol%. In some embodiments, the minimum amount of SrO is about 0.02 mol%. In one or more embodiments, the glass includes BaO in the range of about 0-4.5 mol%, or greater than 0 to about 4.5 mol%, or greater than 1.0 to about 9.0 mol%, or about 1.2-4.4 mol%, or about 2.42-4.3 mol%, or about 2.5-4.5 mol%, or about 2.6-4.4 mol%, or about 3.0-5.4 mol%, or about 3.5-4.0 mol%.

[0106] Summarizing the role / role of the central components of the glasses herein, SiO2 is the basic glass former. Al2O3 and B2O3 are also glass formers and can be selected in pairs, such as increasing B2O3 and correspondingly decreasing Al2O3 to obtain lower density and CTE, while increasing Al2O3 and correspondingly decreasing B2O3 are used to increase annealing point, modulus and durability, provided that the increase in Al2O3 does not reduce the RO / Al2O3 ratio to below about 1.0, where RO = (MgO + CaO + SrO + BaO). If this ratio becomes too low, meltability suffers, i.e., the melting temperature becomes too high. B2O3 can be used to reduce the melting temperature, but high levels of B2O3 are detrimental to the annealing point.

[0107] In addition to meltability and annealing point considerations, for AMLCD applications, the CTE of the glass should be compatible with the CTE of silicon. To achieve such CTE values, exemplary glasses can control the RO content of the glass. For a given Al2O3 content, controlling the RO content corresponds to controlling the RO / Al2O3 ratio. In practice, a glass with a suitable CTE is produced if the RO / Al2O3 ratio is below about 1.6.

[0108] Most importantly for these considerations, it is preferred that the glass be formed by a down-draw process (e.g., a fusion process), which means that the liquidus viscosity of the glass needs to be quite high. Alkaline earth metals alone play an important role in this because they can destabilize the crystalline phase that would otherwise form. BaO and SrO are particularly effective in controlling the liquidus viscosity and are included in the exemplary glasses at least for this purpose. As described in the examples below, various combinations of alkaline earth metals will produce glasses with high liquidus viscosities, and the total amount of alkaline earth metals meets the RO / Al2O3 ratio restrictions required to achieve low melting temperatures, high annealing points, and suitable CTEs. In some embodiments, the liquidus viscosity is greater than or equal to about 150 kP.

[0109] In addition to the above components, the glass compositions described herein may include various other oxides to adjust the various physical, melting, clarification and forming properties of the glass. Examples of such other oxides include, but are not limited to, TiO2, MnO, Fe2O3, ZnO, Nb2O5, MoO3, Ta2O5, WO3, Y2O3, La2O3 and CeO2 as well as other alkaline earth oxides and phosphates. In one embodiment, the amount of each of these oxides may be less than or equal to 2.0 mol%, and the sum of their combined concentrations may be less than or equal to 5.0 mol%. In one embodiment, the amount of ZnO included in the glass composition is about 0-1.5 mol% or about 0-1.0 mol%. The glass compositions described herein also include contaminants associated with batch materials and / or various contaminants introduced into the glass by the melting, clarification and / or forming equipment used to prepare the glass, particularly Fe2O2 and ZrO2. The glass may also contain SnO2 from Joule melting using tin oxide electrodes and / or by batches of tin-containing materials such as SnO2, SnO, SnCO3, SnC2O2, and the like.

[0110] The glass composition is generally free of alkali metals; however, the glass may contain some alkali metal contaminants. In the case of AMLCD applications, it is desirable to keep the alkali level below 0.1 mol % to avoid negatively affecting the performance of the thin film transistor (TFT) by diffusion of alkali ions from the glass into the silicon of the TFT. As used herein, "alkali-free glass" is a glass having a total alkali metal concentration of less than or equal to 0.1 mol %, wherein the total alkali metal concentration is the sum of the concentrations of Na2O, K2O, and Li2O. In one embodiment, the total alkali concentration is less than or equal to 0.1 mol %.

[0111] As described above, a ratio of (MgO+CaO+SrO+BaO) / Al2O3 greater than or equal to 1.0 improves fining, i.e., the removal of gaseous inclusions from the molten batch material. This improvement enables the use of more environmentally friendly fining packages. For example, the glass compositions described herein may have one or more or all of the following compositional characteristics, based on oxides: (i) an As2O3 concentration of up to 0.05 mol%; (ii) an Sb2O3 concentration of up to 0.05 mol%; (iii) an SnO2 concentration of up to 0.25 mol%.

[0112] As2O3 is an effective high temperature fining agent for AMLCD glass, and in some embodiments described herein, As2O3 is used for fining due to its excellent fining properties. However, As2O3 is toxic and requires special handling during the glass manufacturing process. Therefore, in certain embodiments, fining is performed without using a significant amount of As2O3, i.e., the final glass has a maximum of 0.05 mol% As2O3. In one embodiment, As2O3 is not intentionally used in the fining of the glass. In this case, the finished glass will typically have a maximum of 0.005 mol% As2O3 due to contaminants present in the batch material and / or in the equipment used to melt the batch material.

[0113] Although not as toxic as As2O3, Sb2O3 is also toxic and requires special handling. In addition, Sb2O3 increases density, raises CTE, and lowers annealing point compared to glasses using As2O3 or SnO2 as fining agents. Therefore, in certain embodiments, fining is performed without using a significant amount of Sb2O3, i.e., the final glass has at most 0.05 mol% Sb2O3. In another embodiment, Sb2O3 is not intentionally used in the fining of the glass. In this case, the finished glass will typically have at most 0.005 mol% Sb2O3 due to contaminants present in the batch materials and / or in the equipment used to melt the batch materials.

[0114] Tin fining (i.e., SnO2 fining) is less effective than As2O3 and Sb2O3 fining, but SnO2 is a common material with no known hazardous properties. In addition, SnO2 has been a component of AMLCD glasses for many years by using tin oxide electrodes in Joule melting of batch materials for AMLCD glasses. The presence of SnO2 in AMLCD glasses does not result in any known adverse effects when using these glasses to make liquid crystal displays. However, high concentrations of SnO2 are not preferred because this can lead to the formation of crystal defects in the AMLCD glass. In one embodiment, the concentration of SnO2 in the final glass is less than or equal to 0.25 mol%.

[0115] In some embodiments, it was unexpectedly discovered that the higher viscosity glasses described herein can allow for higher SnO2 concentrations without causing any deleterious effects on the glass. For example, common knowledge suggests that glasses with high annealing points result in high melting temperatures. Such high melting temperatures can result in poorer inclusion quality in the corresponding glass. To address such inclusion quality, fining agents can be added; however, glasses with low viscosities generally do not allow for the addition of SnO2 because it crystallizes in the glass. However, the exemplary glasses as described herein can have higher viscosities, resulting in higher forming temperatures, thereby allowing for greater amounts of fining agents to be added to the glass, resulting in fewer inclusions. In short, it was discovered that by changing the composition of the exemplary glass to produce higher temperatures, greater amounts of fining agents can be added to remove inclusions prior to crystallization. Therefore, the exemplary glass can contain SnO2 at a concentration of 0.001-0.5 mol%, T 35kP Greater than or equal to about 1270° C., greater than or equal to about 1280° C., or greater than or equal to about 1290° C. Another exemplary glass may include a SnO2 concentration of 0.001-0.5 mol %, T 200P Greater than or equal to about 1650° C., greater than or equal to about 1660° C., or greater than or equal to about 1670° C. Another exemplary glass may include a SnO2 concentration of 0.001-0.5 mol %, and T 35kP is greater than or equal to about 1270° C., greater than or equal to about 1280° C., or greater than or equal to about 1290° C., and T 200P Greater than or equal to about 1650°C, greater than or equal to about 1660°C, or greater than or equal to about 1670°C. Other exemplary glasses may include SnO2 concentrations of 0.001-0.5 mol % and liquidus temperatures greater than about 1150°C, greater than about 1165°C, or greater than about 1170°C. The glass may also have the T 35kP and / or T 200P Of course, SnO2 can be provided to the glass from Joule melting using tin oxide electrodes and / or by batches of tin-containing materials such as SnO2, SnO, SnCO3, SnC2O2, and the like.

[0116] Tin clarification can be used alone or in combination with other clarification techniques if desired. For example, tin clarification can be combined with halide clarification such as bromine clarification. Other possible combinations include, but are not limited to, tin clarification plus sulfate, sulfide, cerium oxide, mechanical bubbling and / or vacuum clarification. It is expected that these other clarification techniques can be used alone. In certain embodiments, the ratio of (MgO+CaO+SrO+BaO) / Al2O3 and the individual alkaline earth metal concentrations are maintained in the ranges described above, making the clarification process easier to carry out and more effective.

[0117] Various techniques known in the art can be used to make the glasses described herein. In one embodiment, the glass is made using a down-draw process such as a fusion draw process. In one embodiment, described herein is a method for producing an alkali-free glass sheet by a down-draw process, the method comprising: selecting, melting and refining a batch material so that the glass constituting the sheet comprises: SiO2, Al2O3, B2O3, MgO, CaO and BaO, and, calculated as oxides, comprises: (i) a (MgO+CaO+SrO+BaO) / Al2O3 ratio greater than or equal to 1.0; (ii) a MgO content greater than or equal to 3.0 mol%; (iii) a CaO content greater than or equal to 4.0 mol%; and (iv) a BaO content greater than or equal to 1.0 mol%, wherein (a) the refining is performed without the use of significant amounts of arsenic (and optionally, without the use of significant amounts of antimony); and (b) an average gaseous inclusion level of less than 0.10 gaseous inclusions / cm3 for a collection of 50 sequential glass sheets produced by the down-draw process from the melted and refined batch material, wherein the volume of each sheet in the collection is at least 500 cm3.

[0118] U.S. Pat. No. 5,785,726 (Dorfeld et al.), U.S. Pat. No. 6,128,924 (Bange et al.), U.S. Pat. No. 5,824,127 (Bange et al.), and U.S. Pat. Nos. 7,628,038 and 7,628,039 (DeAngelis et al.) disclose processes for making arsenic-free glass. U.S. Pat. No. 7,696,113 (Ellison) discloses a process for making arsenic-free and antimony-free glass using iron and tin to minimize gaseous inclusions.

[0119] According to one embodiment, a collection of 50 sequential glass sheets, each sheet in the collection having a volume of at least 500 cubic centimeters, has an average gaseous inclusion level of less than 0.05 gaseous inclusions per cubic centimeter when produced by a downdraw process from molten and refined batch material.

[0120] The etch rate of a glass composition is a measure of how quickly material can be removed from the glass, and a fast etch rate is found to be valuable to panel manufacturers. The inventors have determined an "etch index" that allows the etch rate of a glass composition in a commercially relevant etching process (e.g., but not limited to, immersion in a 10% HF / 5% HCl solution at 30°C for 10 minutes) to be evaluated. The etch index is defined by the following equation (2):

[0121] Etching index = -54.6147 + (2.50004) * (Al2O3) + (1.3134) * (B2O3) + (1.84106) * (MgO) + (3.01223) * (CaO) + (3.7248) * (SrO) + (4.13149) * (BaO) (2)

[0122] wherein the units of oxide are mol %. In some embodiments, the etch index is greater than or equal to about 21. In various embodiments, the etch index is greater than or equal to about 21.5, 22, 22.5, 23, 23.5, 24, 24.5, 25, 25.5, 26, 26.5, 27, 27.5, 28, 28.5, 29, 29.5, 30, 30.5, or 31.

[0123] Some embodiments herein relate to a glass composition, in terms of mol% of oxides, comprising:

[0124] SiO2 68.5-72.0

[0125] Al2O3≥13.0

[0126] B2O3≤2.5

[0127] MgO 1.0-6.0

[0128] CaO 4.0-8.0

[0129] SrO≤4.5

[0130] BaO≤4.5

[0131] in

[0132] 1.0≤(MgO+CaO+SrO+BaO) / Al2O3≤1.6,

[0133] Etching index ≥21;

[0134] Annealing point ≥ 800°C; and

[0135] Modulus>82GPa.

[0136] One or more embodiments herein are directed to a substantially alkali-free glass comprising, in mole % of oxides:

[0137] SiO2 63.0-71.0

[0138] Al2O3 13.0-14.0

[0139] B2O3>0-3.0

[0140] MgO 0.9-9.0

[0141] CaO 5.25-6.5

[0142] SrO>0-6.0

[0143] BaO 1.0-9.0

[0144] Some embodiments herein are directed to substantially alkali-free glasses, comprising, in mole % of oxides:

[0145] SiO2 68.0-71.0

[0146] Al2O3 13.0-14.0

[0147] B2O3>0-2.0

[0148] MgO 3.5-5.0

[0149] CaO 5.25-6.5

[0150] SrO>0-2.0

[0151] BaO 2.5-4.5

[0152] Some embodiments herein are directed to substantially alkali-free glasses, comprising, in mole % of oxides:

[0153] SiO2 68.0-70.5

[0154] Al2O3 13.0-14.0

[0155] B2O3>0-3.0

[0156] MgO 0.9-9.0

[0157] CaO 5.25-11

[0158] SrO>0-6.0

[0159] BaO 1.0-9.0

[0160] Some embodiments herein are directed to substantially alkali-free glasses, comprising, in mole % of oxides:

[0161] SiO2 68.0-70.5

[0162] Al2O3 13.0-14.0

[0163] B2O3>0-2.0

[0164] MgO 3.5-5.0

[0165] CaO 5.25-10.0

[0166] SrO>0-2.0

[0167] BaO 2.5-4.5

[0168] Some embodiments herein are directed to substantially alkali-free glasses, comprising, in mole % of oxides:

[0169] SiO2 63.0-75.0

[0170] Al2O3 13.0-14.0

[0171] B2O3>0-2.8

[0172] MgO 0.9-9.0

[0173] CaO 5.25-11

[0174] SrO>0-6.0

[0175] BaO 1.0-9.0

[0176] Some embodiments herein are directed to substantially alkali-free glasses, comprising, in mole % of oxides:

[0177] SiO2 68.0-72.0

[0178] Al2O3 13.0-14.0

[0179] B2O3>0-2.0

[0180] MgO 3.5-5.0

[0181] CaO 5.25-10.0

[0182] SrO>0-2.0

[0183] BaO 2.5-4.5

[0184] Some embodiments herein are directed to substantially alkali-free glasses, comprising, in mole % of oxides:

[0185] SiO2 63.0-75.0

[0186] Al2O3 13.0-14.0

[0187] B2O3>0-3.0

[0188] MgO 0.9-9.0

[0189] CaO 5.25-11

[0190] SrO>0-6.0

[0191] BaO 3.0-5.4

[0192] Some embodiments herein are directed to substantially alkali-free glasses, comprising, in mole % of oxides:

[0193] SiO2 68.0-72.0

[0194] Al2O3 13.0-14.0

[0195] B2O3>0-2.0

[0196] MgO 3.5-5.0

[0197] CaO 5.25-10.0

[0198] SrO>0-2.0

[0199] BaO 2.5-4.5

[0200] Some embodiments herein are directed to substantially alkali-free glasses, comprising, in mole % of oxides:

[0201] SiO2 63.0-75.0

[0202] Al2O3 13.0-14.5

[0203] B2O3>0-2.0

[0204] MgO 0.9-9.0

[0205] CaO 5.0-6.5

[0206] SrO>0-6.0

[0207] BaO 1.0-9.0,

[0208] (MgO+CaO+SrO+BaO) / Al2O3 is 1.1-1.6.

[0209] Some embodiments herein are directed to substantially alkali-free glasses, comprising, in mole % of oxides:

[0210] SiO2 68.0-72.0

[0211] Al2O3 13.0-14.5

[0212] B2O3>0-2.0

[0213] MgO 3.5-5.0

[0214] CaO 5.25-6.5

[0215] SrO>0-2.0

[0216] BaO 2.5-4.5

[0217] Some embodiments herein are directed to substantially alkali-free glasses, comprising, in mole % of oxides:

[0218] SiO2 63.0-71.0

[0219] Al2O3 13.0-14.0

[0220] B2O3>0-2.0

[0221] MgO 0.9-9.0

[0222] CaO 5.25-6.5

[0223] SrO>0-6.0

[0224] BaO 1.0-9.0

[0225] Some embodiments herein are directed to substantially alkali-free glasses, comprising, in mole % of oxides:

[0226] SiO2 68.0-71.0

[0227] Al2O3 13.0-14.0

[0228] B2O3>0-2.0

[0229] MgO 3.5-5.0

[0230] CaO 5.25-6.5

[0231] SrO>0-2.0

[0232] BaO 2.5-4.5

[0233] Some embodiments herein are directed to substantially alkali-free glasses, comprising, in mole % of oxides:

[0234] SiO2 63.0-71.0

[0235] Al2O3 13.0-14.0

[0236] B2O3>0-2.0

[0237] MgO 0.9-9.0

[0238] CaO 5.0-6.5

[0239] SrO>0-6.0

[0240] BaO 3.5-4.0

[0241] Some embodiments herein are directed to substantially alkali-free glasses, comprising, in mole % of oxides:

[0242] SiO2 68.0-71.0

[0243] Al2O3 13.0-14.0

[0244] B2O3>0-2.0

[0245] MgO 3.5-5.0

[0246] CaO 5.0-6.5

[0247] SrO>0-2.0

[0248] BaO 3.5-4.0

[0249] Some embodiments herein are directed to substantially alkali-free glasses, comprising, in mole % of oxides:

[0250] SiO2 63.0-71.0

[0251] Al2O3 13.0-14.0

[0252] B2O3>0-2.0

[0253] MgO 0.9-9.0

[0254] CaO 5.0-6.5

[0255] SrO>0-6.0

[0256] BaO 1.0-9.0,

[0257] Among them, the sum of CaO and BaO>8.6.

[0258] Some embodiments herein relate to glasses, in terms of mole % of oxides, comprising:

[0259] SiO2 68.0-71.0

[0260] Al2O3 13.0-14.0

[0261] B2O3>0-2.0

[0262] MgO 3.5-5.0

[0263] CaO 5.0-6.5

[0264] SrO>0-2.0

[0265] BaO 2.5-4.5

[0266] One or more embodiments herein are directed to a substantially alkali-free glass having an annealing temperature of about 785° C. or greater; a density of about 2.65 g / cc or less; and a T 200P Less than or equal to about 1750°C; T 35kP Less than or equal to about 1340°C; Young's modulus greater than or equal to 82 GPa; and Etching index in 10% HF / HCl greater than or equal to about 17.3 μm / mm 3 In a specific embodiment, the glass has an annealing temperature greater than or equal to about 800° C.; a density less than or equal to about 2.61 g / cc; and a T 200P Less than or equal to about 1700°C; T 35kP Less than or equal to about 1310°C; Etching index greater than or equal to about 18.5 μm / mm 3 In some embodiments, the glass article has a T 200P Less than or equal to about 1740°C, or 1730°C, or 1720°C, or 1710°C, or 1700°C, or 1690°C, 1680°C, 1670°C, 1660°C, or 1650°C. In one or more embodiments, the glass article has a T 200P About 1640-1705°C, or about 1646-1702°C, or about 1650-1700°C.

[0267] One or more embodiments herein are directed to a substantially alkali-free glass having one or more of the following properties: an annealing temperature greater than or equal to about 785° C.; a density less than or equal to about 2.65 g / cc; T 200P Less than or equal to about 1750°C; T 35kP Less than or equal to about 1340°C; Young's modulus greater than or equal to 82 GPa; and Etching index in 10% HF / HCl greater than or equal to about 17.3 μm / mm 3 In some embodiments, the glass has one or more of the following properties: annealing temperature greater than or equal to about 800° C.; density less than or equal to about 2.61 g / cc; T 200P Less than or equal to about 1700°C; T 35kP Less than or equal to about 1310°C; or an etching index greater than or equal to about 18.5 μm / mm 3 .

[0268] One or more embodiments herein are directed to a substantially alkali-free glass, in terms of mol% of oxides, comprising:

[0269] SiO2 69.76-71.62

[0270] Al2O3 11.03-13.57

[0271] B2O3 0-2.99

[0272] MgO 3.15-5.84

[0273] CaO 4.55-7.35

[0274] SrO 0.2-1.99

[0275] BaO 2.61-4.41

[0276] ZnO 0-1.0,

[0277] The glass has a (MgO+CaO+SrO+BaO) / Al2O3 ratio of about 1.0-1.6, and a MgO / (MgO+CaO+SrO+BaO) ratio of about 0.22-0.37. In various embodiments, the glass has one or more of the following properties: T (annealed)>785°C; density <2.65 g / cc; T ( 200P )<1750℃; T( 35kP )<1340℃; Young's modulus>82GPa; or etching index>21.

[0278] Some embodiments herein relate to substantially alkali-free glasses, measured in mol % of oxides, comprising:

[0279] SiO2 68.14-72.29

[0280] Al2O3 11.03-14.18

[0281] B2O3 0-2.99

[0282] MgO 1.09-7.2

[0283] CaO 4.12-9.97

[0284] SrO 0.2-4.15

[0285] BaO 1.26-4.41

[0286] ZnO 0-1.0,

[0287] Among them, the ratio of (MgO+CaO+SrO+BaO) / Al2O3 is about 1.0-1.6, and the ratio of MgO / (MgO+CaO+SrO+BaO) is about 0.22-0.37. In various embodiments, the glass has one or more of the following properties: T (annealed)>785°C; density <2.65g / cc; T ( 200P )<1750℃; T( 35kP )<1340℃; Young's modulus>82GPa; or etching index>21μm / mm 3 .

[0288] One or more embodiments herein relate to substantially alkali-free glass, wherein (MgO+CaO+SrO+BaO) / Al2O3 is about 1.0 to 1.6, and the ratio MgO / (MgO+CaO+SrO+BaO) is about 0.22 to 0.37. In some embodiments, the glass has one or more of the following properties: T(annealed)>785°C; density<2.65 g / cc; T( 200P )<1750℃; T( 35kP )<1340℃; Young's modulus>82GPa; or etching index>21μm / mm 3 In various embodiments, the glass comprises, in terms of mole % of oxides, one or more of: SiO2 in the range of 68.14-72.29; Al2O3 in the range of 11.03-14.18; B2O3 in the range of 0-2.99; MgO in the range of 1.09-7.2; CaO in the range of 4.12-9.97; SrO in the range of 0.2-4.15; BaO in the range of 1.26-4.41; and / or ZnO in the range of 0-1.0.

[0289] Some embodiments relate to substantially alkali-free glass, wherein (MgO+CaO+SrO+BaO) / Al2O3 is about 1.0 to 1.6, the ratio MgO / (MgO+CaO+SrO+BaO) is about 0.22 to 0.37, and the liquidus viscosity of the glass is >150 kP. In various embodiments, the glass comprises, in terms of mol % of oxides, one or more of: SiO2 in the range of 68.14-72.29; Al2O3 in the range of 11.03-14.18; B2O3 in the range of 0-2.99; MgO in the range of 1.09-7.2; CaO in the range of 4.12-9.97; SrO in the range of 0.2-4.15; BaO in the range of 1.26-4.41; and / or ZnO in the range of 0-1.0.

[0290] One or more embodiments are directed to a substantially alkali-free glass, wherein (MgO+CaO+SrO+BaO) / Al2O3 is about 1.0 to 1.6, and the etching index of the glass is greater than or equal to 23 μm / mm 3 , T(annealed)>800°C and Young's modulus>82 GPa. In various embodiments, the glass comprises, in terms of mol % of oxides, one or more of: SiO2 in the range of 68.14-72.29; Al2O3 in the range of 11.03-14.18; B2O3 in the range of 0-2.99; MgO in the range of 1.09-7.2; CaO in the range of 4.12-9.97; SrO in the range of 0.2-4.15; BaO in the range of 1.26-4.41; and / or ZnO in the range of 0-1.0.

[0291] Some embodiments herein relate to a substantially alkali-free aluminosilicate glass article, wherein the glass article has an annealing temperature greater than or equal to about 795° C.; a density less than or equal to about 2.63 g / cc; T 200P Less than or equal to about 1730°C; T 35kP Less than or equal to about 1320°C; Young's modulus greater than or equal to 81.5 GPa; and etching index greater than or equal to about 23 μm / mm 3 In various embodiments, the aluminosilicate glass article comprises one or more of: 68.5-72 mol% SiO2; greater than or equal to 13 mol% Al2O3; 0-2.5 mol% B2O3; 1-6 mol% MgO; 4-8 mol% CaO; 0-4.5 mol% SrO; 0-4.5 mol% BaO; and / or a ratio (MgO+CaO+SrO+BaO) / Al2O3 of 1-1.6.

[0292] Some embodiments herein relate to a substantially alkali-free aluminosilicate glass article, wherein the glass article has an annealing temperature of about 800° C. or greater; a density of about 2.61 g / cc or less; and a T 200P Less than or equal to about 1710°C; T 35kP Less than or equal to about 1310°C; Young's modulus greater than or equal to 81.2 GPa; and etching index greater than or equal to about 23 μm / mm 3 In various embodiments, the aluminosilicate glass article comprises one or more of: 68.5-72 mol% SiO2; greater than or equal to 13 mol% Al2O3; 0-2.5 mol% B2O3; 1-6 mol% MgO; 4-8 mol% CaO; 0-4.5 mol% SrO; 0-4.5 mol% BaO; and / or a ratio (MgO+CaO+SrO+BaO) / Al2O3 of 1-1.6.

[0293] It should be understood that multiple disclosed embodiments may relate to specific features, elements or steps described with a specific embodiment. It should be understood that, although specific features, elements or steps are described in conjunction with a specific embodiment, different embodiments may be interchanged or combined with each other in various combinations or permutations not shown.

[0294] It should also be understood that the articles “the,” “a,” or “an” as used herein mean “at least one” and should not be limited to “only one” unless explicitly stated to the contrary.

[0295] Herein, ranges may be expressed as a range from "about" one specific value and / or to "about" another specific value. When expressing such a range, examples include starting from a specific value and / or ending at another specific value. Similarly, when the antecedent "about" is used to indicate that a value is an approximation, it is understood that the specific value constitutes another aspect. It is also understood that the endpoints of each range are meaningful both in relation to the other endpoint and in relation to the other endpoint.

[0296] As used herein, the terms "substantially," "substantially," and variations thereof are intended to mean that the described feature is identical or approximately identical to a value or description. Additionally, "substantially similar" is intended to mean that two values ​​are equal or approximately equal. In some embodiments, "substantially similar" may mean that the values ​​are within about 10% of each other, such as within about 5% of each other, or within about 2% of each other.

[0297] Unless otherwise stated, it is not intended that any method described herein be construed as requiring that its steps be performed in a specific order. Therefore, when a method claim does not actually state that its steps follow a certain order or it does not specifically indicate in any other way in the claims or description that the steps are limited to a specific order, it is not intended to imply any particular order.

[0298] Although the transitional term "comprising" may be used to disclose various features, elements, or steps of a particular embodiment, it should be understood that this implies alternative embodiments including those that may be described using the transitional terms "consisting of," "consisting essentially of." Thus, for example, implicit alternative embodiments for a device comprising A+B+C include embodiments in which the device consists of A+B+C and embodiments in which the device consists essentially of A+B+C.

[0299] It is obvious to those skilled in the art that various modifications and changes can be made to this article without departing from the scope and spirit of this article. Because those skilled in the art can think of various improved combinations, sub-item combinations and changes of the described embodiments that incorporate the spirit and essence of this disclosure, it should be considered that this article includes all the contents within the scope of the attached claims and their equivalents.

[0300] Example

[0301] The following examples are set forth hereinafter to illustrate methods and results according to the disclosed subject matter. These examples are not intended to include all embodiments of the subject matter disclosed herein, but to illustrate representative methods and results. These examples are not intended to exclude equivalents and variations of this article that are obvious to those of ordinary skill in the art.

[0302] Many efforts have been made to ensure accuracy of numerical values ​​(e.g., amounts, temperatures, etc.), but some errors and deviations must be accounted for. Unless otherwise indicated, temperatures are expressed in ° C. or are ambient temperatures, and pressures are at or near atmospheric pressure. The compositions themselves are given in mole % based on the oxides and have been normalized to 100%. There are many variations and combinations of reaction conditions such as component concentrations, temperatures, pressures, and other reaction ranges and conditions that can be used to optimize the product purity and yield obtained from the described processes. Only reasonable and routine experimentation is required to optimize such process conditions.

[0303] The glass properties listed in Table 1 were determined according to conventional techniques in the glass field. Therefore, the linear coefficient of thermal expansion (CTE) in the temperature range of 25-300°C is expressed as x10 -7 / ° C, and the annealing point is expressed in ° C. These are determined by fiber elongation techniques (ASTM references E228-85 and C336, respectively). Density is measured by the Archimedes method (ASTM C693) and is expressed in grams per centimeter 3 The melting temperature (defined as the temperature at which the glass melt demonstrates a viscosity of 200 poise) is calculated using the Fulcher equation (ASTM C965-81) in °C by substituting the high temperature viscosity data measured by the rotating cylinder viscometer.

[0304] The liquidus temperature of the glass is measured in °C using the standard gradient boat liquidus method of ASTM C829-81. This involves placing crushed glass particles in a platinum boat, placing the boat in a furnace with gradient temperature zones, heating the boat in the appropriate temperature zones for 24 hours, and determining the highest temperature at which crystals appear inside the glass by microscopic examination. More specifically, the glass sample is removed from the Pt boat in a piece and examined using a polarized optical microscope to determine the location and nature of crystals formed near the Pt and air interface and inside the sample. Because the gradient of the furnace is well known, the relationship between temperature and location can be well estimated to within 5-10 °C. The temperature at which crystals are observed in the inner portion of the sample is considered to represent the liquidus of the glass (for the corresponding test period). Tests are sometimes performed for longer periods of time (e.g., 72 hours) to observe slower growing phases. The liquidus viscosity is determined from the liquidus temperature and the coefficients of the Fulcher equation in poise.

[0305] Young's modulus values ​​are determined using resonant ultrasonic spectroscopy techniques of the general type described in ASTM E1875-00e1 and are reported in GPa.

[0306] Exemplary glasses are shown in Table 1. As can be seen from Table 1, the exemplary glasses have density, annealing point, and Young's modulus values ​​that make the glasses suitable for display applications (e.g., AMLCD substrate displays), more specifically for low temperature polysilicon and oxide thin film transistor applications. Although not shown in Table 1, the durability of the glasses in acid and alkaline media is similar to those of commercially available AMLCD substrates and is therefore suitable for AMLCD applications. With the above criteria, the exemplary glasses can be formed using down-draw techniques, and are particularly compatible with fusion processes.

[0307] The exemplary glasses of Table 1 were prepared using commercially available sand as the silica source (which was ground to such an extent that 90 wt. % passed through a standard US100 mesh screen). Alumina was the source of alumina, periclase was the source of MgO, limestone was the source of CaO, strontium carbonate, strontium nitrate or a mixture thereof was the source of SrO, barium carbonate was the source of BaO, and tin (IV) oxide was the source of SnO2. The raw materials were thoroughly mixed, loaded into a platinum container suspended in a furnace heated by a silicon carbide glowbar, melted at a temperature of 1600-1650°C and stirred for several hours to ensure homogenization, and delivered through a hole located in the base of the platinum container. The resulting glass cake was annealed at or near the annealing point and then subjected to various experimental methods to determine physical, viscosity and liquidus properties.

[0308] These methods are not exclusive, and standard methods well known to those skilled in the art can be used to prepare the glasses of Table 1. Such methods include continuous melting methods, such as would be performed in a continuous melting process, wherein the melter used in the continuous melting process is heated by gas, by electricity, or a combination thereof.

[0309] Raw materials suitable for producing exemplary glasses include: commercially available sand as a source of SiO2; aluminum oxide, aluminum hydroxide, aluminum oxide in hydrated form, and various aluminosilicates, nitrates, and halides as a source of Al2O3; boric acid, anhydrous boric acid, and boric oxide as a source of B2O3; periclase, dolomite (also a source of CaO), magnesium oxide, magnesium carbonate, magnesium hydroxide, and various forms of magnesium silicates, magnesium aluminosilicates, magnesium nitrates, and magnesium halides as a source of MgO; limestone, aragonite, dolomite (also a source of MgO), wollastonite, and various forms of calcium silicates, calcium aluminosilicates, calcium nitrates, and calcium halides as a source of CaO; and oxides, carbonates, nitrates, and halides of strontium and barium. If a chemical fining agent is desired, tin can be added as SnO2, as a mixed oxide with other major glass components (e.g., CaSnO3), or as an oxidized state SnO, tin oxalate, tin halide, or other tin-containing compounds known to those skilled in the art.

[0310] The glasses in Table 1 contain SnO2 as a fining agent, but other chemical fining agents may also be used to obtain glasses of sufficient quality for TFT substrate applications. For example, the exemplary glasses may use any one or combination of As2O3, Sb2O3, CeO2, Fe2O3 and halides as intentional additions to promote fining, and any of these may be used in conjunction with the SnO2 chemical fining agent shown in the Examples. Of these, As2O3 and Sb2O3 are generally considered to be hazardous materials and are subject to waste stream control, such as waste streams that may be generated during the glass manufacturing process or TFT panel processing. Therefore, it is desirable to limit the concentration of As2O3 and Sb2O3, alone or in combination, to no more than 0.005 mol%.

[0311] In addition to the elements intentionally incorporated into the exemplary glasses, almost all stable elements in the periodic table are present in the glass at some level, either as contaminants in the raw materials at low levels, by high temperature corrosion of refractory materials and precious metals during the manufacturing process, or by intentional introduction at low levels to fine tune the properties of the final glass. For example, zirconium may be introduced as a contaminant through interaction with zirconium-rich refractory materials. For another example, platinum and rhodium may be introduced through interaction with precious metals. For another example, iron may be introduced as a tramp in the raw materials or intentionally added to enhance control of gaseous inclusions. For another example, manganese may be introduced to control color or to enhance control of gaseous inclusions. For another example, alkali metals may be present as an uncertain component, combined with the concentrations of Li2O, Na2O, and K2O, at levels up to about 0.1 mol%.

[0312] Hydrogen inevitably forms in the form of hydroxyl anions (OH - ) in the form of a molten metal, the presence of which can be detected by standard infrared spectroscopy techniques. Dissolved hydroxide ions significantly and nonlinearly affect the annealing point of the exemplary glass, so in order to obtain the desired annealing point, it may be necessary to adjust the concentration of the main oxide component to compensate. The hydroxide ion concentration can be controlled to a certain extent by selecting raw materials or selecting a melting system. For example, boric acid is the main source of hydroxide, and replacing boric acid with boron oxide can be a useful method to control the hydroxide concentration in the final glass. The same reasoning applies to other potential raw materials, including hydroxide ions, hydrates, or compounds containing physically adsorbed or chemically adsorbed water molecules. If a burner is used in the melting process, hydroxide ions can also be introduced through the combustion products of natural gas and related hydrocarbon combustion, so it may be desirable to convert the energy used in the melting from the burner to the electrode to compensate. Alternatively, an iterative process of adjusting the main oxide component can be used instead to compensate for the adverse effects of dissolved hydroxide ions.

[0313] Sulfur is commonly present in natural gas and can be an unspecified component of many carbonate, nitrate, halide and oxide raw materials. In the form of SO2, sulfur can be a troublesome source of gaseous inclusions. By controlling the level of sulfur in the raw materials, and by incorporating low levels of comparable reducing multivalent cations into the glass matrix, the tendency to form SO2-rich defects can be controlled to a significant extent. While not wishing to be bound by theory, it appears that the formation of SO2-rich defects is primarily through the presence of sulfates (SO4) dissolved in the glass. = ) to produce SO2-rich gaseous inclusions. It appears that the increased barium concentration of the exemplary glass increases the retention of sulfur in the glass in the early stages of melting, but as mentioned above, barium is required to obtain a low liquidus temperature and thus a high T 35k -T 液相and high liquidus viscosity. Intentionally controlling the sulfur level in the raw materials to a low level is a useful means of reducing the sulfur (assuming sulfate) dissolved in the glass. Specifically, in the batch material, sulfur is preferably less than 200 ppm, more preferably less than 100 ppm by weight.

[0314] Reducing polyvalents can also be used to control the tendency of the exemplary glasses to form SO2 bubbles. Although not wishing to be bound by theory, these elements act as potential electron donors, which suppress the electromotive force of sulfate reduction. Sulfate reduction can be written by half reactions, such as

[0315] SO4 = →SO2+O2+2e -

[0316] Among them, e - represents electrons. The "equilibrium constant" for the half-reaction is

[0317] K eq =[SO2][O2][e - ] 2 / [SO4 = ]

[0318] The brackets indicate chemical activity. Ideally, we would like to promote the reaction so that SO2, O2 and 2e - Sulfate is produced. Adding nitrates, peroxides or other oxygen-rich raw materials in the early stages of melting can help but also hinder sulfate reduction, which can offset the benefit of adding them initially. SO2 has very low solubility in most glasses, so it is not practical to add to the glass melting process. Electrons can be "added" by reducing multivalent species. For example, for ferrous ions (Fe 2+ ) can be expressed as

[0319] 2Fe 2+ →2Fe 3+ +2e -

[0320] This electron "activity" can promote the sulfate reduction reaction to the left, making the SO4 = Stabilization. Suitable reducing polyvalent species include, but are not limited to, Fe 2+ , Mn 2+ Sn 2+ , Sb 3+ 、As 3+ 、V 3+ 、Ti 3+, and others that are well known to those skilled in the art. In each case, it may be important to minimize the concentration of such components to avoid adverse effects on glass color, or in the case of As and Sb, to avoid such components being at levels high enough to complicate waste management in end-user processes.

[0321] In addition to the major oxide components of the exemplary glasses and the minor or indeterminate components described above, halides may be present at various levels, either as contaminants introduced through the selection of raw materials, or as intentionally used components to eliminate gaseous inclusions in the glass. As fining agents, halides may be included at levels less than or equal to about 0.4 mol%, although it is generally desirable to use lower amounts if possible to avoid corrosion of tail gas treatment equipment. In some embodiments, for each individual halide, the concentration of the individual halide element is less than about 200 ppm by weight, or the sum of all halide elements is less than about 800 ppm by weight.

[0322] In addition to these major oxide components, minor and indeterminate components, polyvalents and halide fining agents, it is useful to include other colorless oxide components in low concentrations to achieve the desired physical, optical or viscoelastic properties. Such oxides include, but are not limited to: TiO2, ZrO2, HfO2, Nb2O5, Ta2O5, MoO3, WO3, ZnO, In2O3, Ga2O3, Bi2O3, GeO2, PbO, SeO3, TeO2, Y2O3, La2O3, Gd2O3 and others known to those skilled in the art. By an iterative process of adjusting the relative proportions of the major oxide components of the exemplary glasses, levels of up to about 2 mole percent of such colorless oxides may be added without affecting the annealing point, T 35k -T 液相线 or liquidus viscosity has an unacceptable effect.

[0323] Table 1 shows that T (annealing)>795℃, Young's modulus>81.5; and etching index>23, density<2.63, T ( 200P )<1730℃; and T( 35kP )<1320°C (Samples 1-189). Table 2 shows additional examples of glasses approaching the parameters of Table 1 (Samples 190-426).

[0324] Table 1

[0325]

[0326] Table 1 (continued)

[0327]

[0328] Table 1 (continued)

[0329]

[0330]

[0331] Table 1 (continued)

[0332]

[0333]

[0334] Table 1 (continued)

[0335]

[0336]

[0337] Table 1 (continued)

[0338]

[0339] Table 1 (continued)

[0340]

[0341]

[0342] Table 1 (continued)

[0343]

[0344]

[0345] Table 1 (continued)

[0346]

[0347]

[0348] Table 1 (continued)

[0349]

[0350] Table 1 (continued)

[0351]

[0352] Table 1 (continued)

[0353]

[0354]

[0355] Table 1 (continued)

[0356]

[0357]

[0358] Table 1 (continued)

[0359]

[0360]

[0361] Table 1 (continued)

[0362]

[0363] Table 1 (continued)

[0364]

[0365]

[0366] Table 1 (continued)

[0367]

[0368]

[0369] Table 1 (continued)

[0370]

[0371]

[0372] Table 1 (continued)

[0373]

[0374] Table 1 (continued)

[0375]

[0376]

[0377] Table 1 (continued)

[0378]

[0379]

[0380] Table 1 (continued)

[0381]

[0382]

[0383] Table 1 (continued)

[0384]

[0385] Table 1 (continued)

[0386]

[0387] Table 2

[0388]

[0389] Table 2 (continued)

[0390]

[0391]

[0392] Table 2 (continued)

[0393]

[0394]

[0395] Table 2 (continued)

[0396]

[0397] Table 2 (continued)

[0398]

[0399] Table 2 (continued)

[0400]

[0401]

[0402] Table 2 (continued)

[0403]

[0404]

[0405] Table 2 (continued)

[0406]

[0407] Table 2 (continued)

[0408]

[0409]

[0410] Table 2 (continued)

[0411]

[0412]

[0413] Table 2 (continued)

[0414]

[0415]

[0416] Table 2 (continued)

[0417]

[0418] Table 2 (continued)

[0419]

[0420]

[0421] Table 2 (continued)

[0422]

[0423]

[0424] Table 2 (continued)

[0425]

[0426]

[0427] Table 2 (continued)

[0428]

[0429] Table 2 (continued)

[0430]

[0431]

[0432] Table 2 (continued)

[0433]

[0434]

[0435] Table 2 (continued)

[0436]

[0437]

[0438] Table 2 (continued)

[0439]

[0440] Table 2 (continued)

[0441]

[0442]

[0443] Table 2 (continued)

[0444]

[0445]

[0446] Table 2 (continued)

[0447]

[0448]

[0449] Table 2 (continued)

[0450]

[0451] Table 2 (continued)

[0452]

[0453]

[0454] Table 2 (continued)

[0455]

[0456]

[0457] Table 2 (continued)

[0458]

[0459] Table 2 (continued)

[0460]

[0461] Table 2 (continued)

[0462]

[0463]

[0464] Table 2 (continued)

[0465]

[0466]

[0467] This application also relates to the following items.

[0468] 1. A glass comprising, in terms of mole % of oxides: SiO2 68.5-72.0, Al2O3 greater than or equal to about 13.0, B2O3 less than or equal to about 2.5, MgO 1.0-6.0, CaO 4.0-8.0, SrO less than or equal to about 4.5, BaO less than or equal to about 4.5, such that (MgO+CaO+SrO+BaO) / Al2O3 is less than or equal to about 1.6, and the glass has an etching index greater than or equal to about 23, an annealing point greater than or equal to about 800°C and a modulus greater than 82 GPa.

[0469] 2. A glass, in terms of mole % of oxides, comprising: SiO2 63.0-71.0, Al2O3 13.0-14.0, B2O3>0-3.0, MgO 0.9-9.0, CaO 5.25-6.5, SrO>0-6.0, BaO 1.0-9.0, the glass being substantially free of alkali metals and having an etching index>21 μm / mm 3 .

[0470] 3. The glass as described in item 2 is characterized in that, in terms of mole % of oxides, the glass comprises: SiO2 68.0-71.0, B2O3>0-2.0, MgO 3.5-5.0, SrO>0-2.0, BaO 2.5-4.5.

[0471] 4. A glass, in terms of mole % of oxides, comprising: SiO2 68.0-70.5, Al2O3 13.0-14.0, B2O3>0-3.0, MgO 0.9-9.0, CaO 5.25-11, SrO>0-6.0, BaO 1.0-9.0, the glass being substantially free of alkali metals and having an etching index>21 μm / mm 3 .

[0472] 5. The glass according to claim 4, characterized in that, in terms of mole % of oxides, the glass comprises: B2O3>0-2.0, MgO 3.5-5.0, CaO 5.25-10.0, SrO>0-2.0, BaO 2.5-4.5.

[0473] 6. A glass, in terms of mole % of oxides, comprising: SiO2 63.0-75.0, Al2O3 13.0-14.0, B2O3>0-2.8, MgO 0.9-9.0, CaO 5.25-11, SrO>0-6.0, BaO 1.0-9.0, the glass being substantially free of alkali metals and having an etching index>21 μm / mm 3 .

[0474] 7. The glass according to item 6, characterized in that, in terms of mole % of oxides, the glass comprises: SiO2 68.0-72.0, B2O3>0-2.0, MgO 3.5-5.0, CaO 5.25-10.0, SrO>0-2.0, BaO 2.5-4.5.

[0475] 8. A glass, in terms of mole % of oxides, comprising: SiO2 63.0-75.0, Al2O3 13.0-14.0, B2O3>0-3.0, MgO 0.9-9.0, CaO 5.25-11, SrO>0-6.0, BaO 3.0-5.4, the glass being substantially free of alkali metals and having an etching index>21 μm / mm 3 .

[0476] 9. The glass according to item 8, characterized in that, in terms of mole % of oxides, the glass comprises: SiO2 68.0-72.0, B2O3>0-2.0, MgO 3.5-5.0, CaO 5.25-10.0, SrO>0-2.0, BaO 2.5-4.5.

[0477] 10. A glass, in terms of mole % of oxides, comprising: SiO2 63.0-75.0, Al2O3 13.0-14.5, B2O3>0-2.0, MgO 0.9-9.0, CaO 5.0-6.5, SrO>0-6.0, BaO1.0-9.0, the glass being substantially free of alkali metals, (MgO+CaO+SrO+BaO) / Al2O3 being 1.1-1.6, and having an etching index>21 μm / mm 3 .

[0478] 11. The glass according to item 10, characterized in that, in terms of mole % of oxides, the glass comprises: SiO2 68.0-72.0, MgO 3.5-5.0, CaO 5.25-6.5, SrO>0-2.0, BaO 2.5-4.5.

[0479] 12. A glass comprising, in terms of mole % of oxides: SiO2 63.0-71.0, Al2O3 13.0-14.0, B2O3>0-2.0, MgO 0.9-9.0, CaO 5.25-6.5, SrO>0-6.0, BaO 1.0-9.0, the glass being substantially free of alkali metals and having an etching index>21 μm / mm 3 .

[0480] 13. The glass according to item 12, characterized in that, in terms of mole % of oxides, the glass comprises: SiO2 68.0-71.0, MgO 3.5-5.0, SrO>0-2.0, BaO 2.5-4.5.

[0481] 14. A glass, in terms of mole % of oxides, comprising: SiO2 63.0-71.0, Al2O3 13.0-14.0, B2O3>0-2.0, MgO 0.9-9.0, CaO 5.0-6.5, SrO>0-6.0, BaO3.5-4.0, the glass being substantially free of alkali metals and having an etching index>21 μm / mm 3 .

[0482] 15. The glass according to item 14, characterized in that, in terms of mole % of oxides, the glass comprises: SiO2 68.0-71.0, MgO 3.5-5.0, SrO>0-2.0.

[0483] 16. A glass, in terms of mole % of oxides, comprising: SiO2 63.0-71.0, Al2O3 13.0-14.0, B2O3>0-2.0, MgO 0.9-9.0, CaO 5.0-6.5, SrO>0-6.0, BaO1.0-9.0, the sum of CaO and BaO>8.6, the glass being substantially free of alkali metals and having an etching index>21 μm / mm 3 .

[0484] 17. The glass according to item 16, characterized in that, in terms of mole % of oxides, the glass comprises: SiO2 68.0-71.0, MgO 3.5-5.0, SrO>0-2.0, BaO 2.5-4.5.

[0485] 18. A glass, comprising:

[0486] an annealing temperature of greater than or equal to about 785°C;

[0487] A density of less than or equal to about 2.65 g / cc;

[0488] T less than or equal to about 1750°C 200P ;

[0489] T less than or equal to about 1340°C 35kP ;

[0490] a Young's modulus greater than or equal to about 82 GPa; and

[0491] Greater than or equal to about 21 μm / mm 3The etching index is defined by the following equation:

[0492] -54.6147+(2.50004)*(Al2O3)+(1.3134)*(B2O3)+(1.84106)*(MgO)+(3.01223)*(CaO)+(3.7248)*(SrO)+(4.13149)*(BaO),

[0493] Wherein, the glass substantially does not contain alkali metals.

[0494] 19. The glass according to item 18, characterized in that the annealing temperature is greater than or equal to about 800°C.

[0495] 20. The glass of items 18-19, wherein the density is less than or equal to about 2.61 g / cc.

[0496] 21. The glass according to items 18-20, characterized in that the T 200P Less than or equal to about 1700°C.

[0497] 22. The glass according to item 18-21, characterized in that the T 35kP Less than or equal to about 1310°C.

[0498] 23. The glass according to items 19-22, characterized in that the predicted etching index is greater than or equal to about 21 μm / mm 3 .

[0499] 24. The glass according to any one of items 18 to 23, wherein the glass comprises SiO2, and the range of SiO2 is 68.1-72.3 in terms of mole % of oxide.

[0500] 25. The glass according to any one of items 18 to 24, wherein the glass comprises Al2O3, and the range of Al2O3 is 11.0-14.0 in terms of mol % of oxide.

[0501] 26. The glass according to any one of items 18 to 25, wherein the glass comprises B2O3, and the range of B2O3, calculated as mol% of oxide, is >0-3.0.

[0502] 27. The glass according to any one of items 18 to 26, wherein the glass comprises MgO, and the MgO content is in the range of 1.0 to 7.2, expressed as a mol % of oxide.

[0503] 28. The glass according to item 27, characterized in that the glass contains MgO, and the range of MgO is 3.1-5.8 in terms of mol % of oxide.

[0504] 29. The glass according to any one of items 18 to 28, wherein the glass comprises CaO, and the range of CaO is 4.1-10.0 in terms of mol % of oxide.

[0505] 30. The glass according to item 29, characterized in that the glass contains CaO, and the range of CaO is 4.5-7.4 in terms of mol % of oxide.

[0506] 31. The glass according to any one of items 18 to 30, wherein the glass comprises SrO, and the range of SrO, expressed as mol % of oxide, is >0-4.2.

[0507] 32. The glass according to claim 31, wherein the glass comprises SrO, and the range of SrO is >0-2.0 in terms of mol % of oxide.

[0508] 33. The glass according to any one of items 18 to 32, characterized in that the glass contains BaO, and the BaO content is in the range of 1.2 to 4.4, calculated as mol % of oxide.

[0509] 34. The glass according to item 33, characterized in that the glass contains BaO, and the BaO ranges from 2.6 to 4.4 in terms of mol % of oxide.

[0510] 35. The glass according to any one of items 18 to 23, characterized in that, in terms of mol % of oxides, the glass comprises: SiO2 68.0-72.0, B2O3 0.1-3.0 and CaO 5.0-6.5.

[0511] 36. The glass according to any one of items 18 to 23, characterized in that, in terms of mol % of oxides, the glass comprises: Al2O3 13.0-14.0, B2O3 0.1-3.0 and CaO 5.25-6.0.

[0512] 37. A glass substantially free of alkali metals, comprising, in terms of mole % of oxides: SiO2 69.76-71.62, Al2O3 11.03-13.57, B2O3 0-2.99, MgO 3.15-5.84, CaO 4.55-7.35, SrO 0.2-1.99, BaO 2.61-4.41 and ZnO 0-1.0, wherein the ratio (MgO+CaO+SrO+BaO) / Al2O3 is about 1.0 to 1.6, and the ratio MgO / (MgO+CaO+SrO+BaO) is about 0.22 to 0.37.

[0513] 38. A glass substantially free of alkali metals, comprising, in terms of mole % of oxides: SiO2 68.14-72.29, Al2O3 11.03-14.18, B2O3 0-2.99, MgO 1.09-7.2, CaO 4.12-9.97, SrO 0.2-4.15, BaO 1.26-4.41 and ZnO 0-1.0, wherein the ratio (MgO+CaO+SrO+BaO) / Al2O3 is about 1.0 to 1.6, and the ratio MgO / (MgO+CaO+SrO+BaO) is about 0.22 to 0.37.

[0514] 39. The glass according to items 37-38, characterized in that the T (annealing) of the glass is > 785°C.

[0515] 40. The glass of items 37-39, wherein the density of the glass is <2.65 g / cc.

[0516] 41. The glass according to items 37-40, characterized in that T(200P) of the glass is less than 1750°C.

[0517] 42. The glass according to items 37-41, characterized in that T(35kP) of the glass is <1340°C.

[0518] 43. The glass according to items 37-42, characterized in that the Young's modulus of the glass is >82 GPa.

[0519] 44. The glass according to item 37-44, characterized in that the etching index of the glass is >21 μm / mm 3 .

[0520] 45. A glass substantially free of alkali metals, wherein (MgO+CaO+SrO+BaO) / Al2O3 is about 1.0 to 1.6, the ratio MgO / (MgO+CaO+SrO+BaO) is about 0.22 to 0.37, T(annealed)>785°C, density<2.65 g / cc, T(200P)<1750°C, T(35kP)<1340°C, Young's modulus>82 GPa, and etching index>21 μm / mm 3 .

[0521] 46. ​​A glass substantially free of alkali metals, wherein (MgO+CaO+SrO+BaO) / Al2O3 is about 1.0-1.6, the ratio MgO / (MgO+CaO+SrO+BaO) is about 0.22-0.37, and the etching index is >21 μm / mm 3 .

[0522] 47. The glass of any of items 1-46, having a liquidus viscosity greater than or equal to about 150 kP.

[0523] 48. A glass substantially free of alkali metals, wherein (MgO+CaO+SrO+BaO) / Al2O3 is about 1.0-1.6, the ratio MgO / (MgO+CaO+SrO+BaO) is about 0.22-0.37, and the liquidus viscosity is >150 kP.

[0524] 49. A glass substantially free of alkali metals, wherein (MgO+CaO+SrO+BaO) / Al2O3 is about 1.0 to 1.6, and the etching index is greater than or equal to 21 μm / mm 3 , T(annealing)>800℃ and Young's modulus>82GPa.

[0525] 50. The glass according to items 45-49, wherein the glass comprises SiO2, and the range of SiO2 is 68.14-72.29 in terms of mole % of oxide.

[0526] 51. The glass according to items 45-50, characterized in that the glass contains Al2O3, and the range of Al2O3 is 11.03-14.18 in terms of mol% of oxide.

[0527] 52. The glass according to items 45-51, characterized in that the glass contains B2O3, and the range of B2O3 is 0-2.99 in terms of mole % of oxide.

[0528] 53. The glass according to items 45-52, characterized in that the glass contains MgO, and the range of MgO is 1.09-7.2 in terms of mol % of oxide.

[0529] 54. The glass according to items 45-53, characterized in that the glass contains CaO, and the range of CaO is 4.12-9.97 in terms of mol % of oxide.

[0530] 55. The glass according to items 45-54, characterized in that the glass contains SrO, and the range of SrO is 0.2-4.15 in terms of mol % of oxide.

[0531] 56. The glass according to items 45-55, characterized in that the glass contains BaO, and the BaO range is 1.26-4.41 in terms of mol % of oxide.

[0532] 57. The glass according to items 45-56, characterized in that the glass contains ZnO, and the range of ZnO is 0-1.0 in terms of mol % of oxide.

[0533] 58. A substantially alkali-free aluminosilicate glass article, wherein the glass article has:

[0534] an annealing temperature of greater than or equal to about 795°C;

[0535] A density of less than or equal to about 2.63 g / cc;

[0536] T less than or equal to about 1730°C 200P ;

[0537] T less than or equal to about 1320°C 35kP ;

[0538] a Young's modulus greater than or equal to about 81.5 GPa; and

[0539] Greater than or equal to about 23 μm / mm 3 Etching index.

[0540] 59. A substantially alkali-free aluminosilicate glass article, wherein the glass article has:

[0541] An annealing temperature of greater than or equal to about 800°C;

[0542] A density of less than or equal to about 2.61 g / cc;

[0543] T less than or equal to about 1710°C 200P ;

[0544] T less than or equal to about 1310°C 35kP ;

[0545] A Young's modulus of greater than or equal to about 81.2 GPa; and

[0546] Greater than or equal to about 23 μm / mm 3 Etching index.

[0547] 60. An aluminosilicate glass product as described in items 58-59, characterized in that the product contains 68.5-72 mol% SiO2.

[0548] 61. An aluminosilicate glass article as described in items 58-60, characterized in that the article contains greater than or equal to 13 mol% A12O3.

[0549] 62. An aluminosilicate glass product as described in items 58-61, characterized in that the product contains 0-2.5 mol% B2O3.

[0550] 63. The aluminosilicate glass article of items 58-62, wherein the article comprises 1-6 mol % MgO.

[0551] 64. The aluminosilicate glass article of items 58-63, wherein the article comprises 4-8 mol% CaO.

[0552] 65. The aluminosilicate glass article of items 58-64, wherein the article comprises 0-4.5 mol% SrO.

[0553] 66. The aluminosilicate glass article of items 58-65, wherein the article comprises 0-4.5 mol% BaO.

[0554] 67. An aluminosilicate glass product as described in items 58-66, characterized in that the product has a (MgO+CaO+SrO+BaO) / Al2O3 ratio of 1-1.6.

[0555] 68. The glass of any one of items 1-67, further comprising about 0.01-0.4 mol % of any one or combination of the following as a chemical fining agent: SnO2, As2O3, Sb2O3, F, Cl and / or Br.

[0556] 69. The glass according to any one of items 1 to 68, further comprising about 0.005-0.2 mol % of any one or combination of the following as a chemical fining agent: Fe2O3, CeO2 or MnO2.

[0557] 70. The glass of any one of items 1-69, wherein As2O3 and Sb2O3 comprise less than about 0.005 mol%.

[0558] 71. An object comprising the glass of any one of items 1-70, wherein the object is produced by a down-drawn sheet manufacturing process.

[0559] 72. An object comprising the glass of any of items 1-70, wherein the object is produced by a fusion process or a variation thereof.

[0560] 73. A liquid crystal display substrate comprising the glass according to any one of items 1-70.

[0561] 74. A glass comprising:

[0562] T greater than or equal to about 1270°C 35kP ;

[0563] SnO2 at a concentration of about 0.001-0.5 mol%;

[0564] and greater than or equal to about 21 μm / mm 3 Etching index.

[0565] 75. The glass of item 74, wherein the glass comprises a T greater than or equal to about 1650°C. 200P .

[0566] 76. The glass of any of items 74-75, wherein the glass comprises a liquidus temperature greater than about 1150°C.

[0567] 77. The glass of any one of items 74-76, wherein the etching index is defined by the following equation: -54.6147+(2.50004)*(Al2O3)+(1.3134)*(B2O3)+(1.84106)*(MgO)+(3.01223)*(CaO)+(3.7248)*(SrO)+(4.13149)*(BaO).

[0568] 78. The glass of any one of items 74-77, wherein the glass further comprises a Young's modulus greater than or equal to about 82 GPa.

[0569] 79. The glass according to any one of items 74 to 78, wherein the glass is substantially free of alkali metals.

[0570] 80. A glass, comprising:

[0571] T greater than or equal to about 1650°C 200P ;

[0572] SnO2 at a concentration of about 0.001-0.5 mol %; and

[0573] Greater than or equal to about 21 μm / mm 3 Etching index.

[0574] 81. A glass, comprising:

[0575] A liquidus temperature of greater than or equal to about 1150°C;

[0576] SnO2 at a concentration of about 0.001-0.5 mol %; and

[0577] Greater than or equal to about 21 μm / mm 3 Etching index.

[0578] 82. A glass, comprising:

[0579] T greater than or equal to about 1270°C 35kP ;as well as

[0580] The concentration is about 0.001-0.5 mol% SnO2.

[0581] 83. The glass of item 82, wherein the glass comprises a T greater than or equal to about 1650°C. 200P .

[0582] 84. The glass of any of items 82-83, wherein the glass comprises a liquidus temperature greater than about 1150°C.

[0583] 85. The glass of any of items 82-84, further comprising a Young's modulus greater than or equal to about 82 GPa.

[0584] 86. The glass of any one of items 82-85, wherein the glass is substantially free of alkali metals.

[0585] 87. A glass, comprising:

[0586] T greater than or equal to about 1650°C 200P ;as well as

[0587] The concentration is about 0.001-0.5 mol% SnO2.

Claims

1. A method for forming glass, the method comprising: Introducing glass into a trough of an isopipe such that the glass overflows over the weir wall of the trough on either side of the isopipe in the form of two streams, wherein the two streams contact edge guides on either side of the isopipe and then rejoin at the root of the isopipe to form a glass sheet, wherein the glass comprises: 68.5 mol% to 72.0 mol% SiO2; Greater than or equal to 13.0 mol% Al2O3; Greater than or equal to 0 mol % to 2.5 mol % B2O3; 1.0 mol% to 6.0 mol% MgO; 4.0 mol% to 8.0 mol% CaO; Less than or equal to 4.5 mol% SrO; Less than or equal to 4.5 mol% BaO; A liquidus viscosity greater than or equal to 150 kpoise; Annealing point greater than or equal to 800°C; Young's modulus greater than 82 GPa; and An etch index greater than or equal to 24, wherein the etch index is equal to -54.6147+(2.50004)*(Al2O3)+(1.3134)*(B2O3)+(1.84106)*(MgO)+(3.01223)*(CaO)+(3.7248)*(SrO)+(4.13149)*(BaO), wherein Al2O3, B2O3, MgO, CaO, SrO and BaO are expressed in mole percentages.

2. The method of claim 1, wherein the glass comprises: 68.5 mol% to 70.5 mol% SiO2; Greater than or equal to 13.0 mol% Al2O3; Greater than 0 mol% to 2.0 mol% B2O3; 3.5 mol% to 5.0 mol% MgO; and 3.5 mol % to 4.0 mol % BaO.

3. The method of claim 1 or claim 2, wherein the glass comprises an etching index greater than 25.

5.

4. The method of claim 1 or claim 2, wherein the glass comprises 13.0 mol% to 14.0 mol% Al2O3.

5. The method of claim 1 or claim 2, wherein the glass comprises 5.25 mol% to 6.0 mol% CaO.

6. The method of claim 1 or claim 2, wherein the glass comprises greater than 2.0 mol% SrO.

7. The method according to claim 1 or claim 2, wherein (MgO+CaO+SrO+BaO) / Al2O3 is 1.1 to 1.

6.

8. The method of claim 1 or claim 2, wherein the sum of CaO and BaO is greater than 8.6 mol%.

9. The method of claim 1 or claim 2, wherein the glass comprises: Density less than or equal to 2.65 g / cc; T200P temperature less than or equal to 1750°C; and T35kP temperature less than or equal to 1340°C.

10. The method of claim 1 or claim 2, further comprising thinning the glass sheet in the etching solution.

11. A glass comprising: 68.5 mol% to 72.0 mol% SiO2; Greater than or equal to 13.0 mol% Al2O3; Greater than or equal to 0 mol % to 2.5 mol % B2O3; 1.0 mol% to 6.0 mol% MgO; 4.0 mol% to 8.0 mol% CaO; Less than or equal to 4.5 mol% SrO; Less than or equal to 4.5 mol% BaO, where (MgO+CaO+SrO+BaO) / Al2O3 is less than or equal to 1.6; A liquidus viscosity greater than or equal to 150 kpoise; Annealing point greater than or equal to 800°C; Young's modulus greater than 82 GPa; and An etching index greater than or equal to 25.5, wherein the etching index is equal to -54.6147+(2.50004)*(Al2O3)+(1.3134)*(B2O3)+(1.84106)*(MgO)+(3.01223)*(CaO)+(3.7248)*(SrO)+(4.13149)*(BaO), wherein Al2O3, B2O3, MgO, CaO, SrO and BaO are expressed in mole percentages.

12. A glass comprising: 68.5 mol% to 70.5 mol% SiO2; Greater than or equal to 13.0 mol% Al2O3; Greater than 0 mol% to 2.0 mol% B2O3; 3.5 mol% to 5.0 mol% MgO; 4.0 mol% to 8.0 mol% CaO; Less than or equal to 4.5 mol% SrO; 3.5 mol% to 4.0 mol% BaO, wherein (MgO+CaO+SrO+BaO) / Al2O3 is less than or equal to 1.17; A liquidus viscosity greater than or equal to 150 kpoise; Annealing point greater than or equal to 800°C; Young's modulus greater than 82 GPa; and An etch index greater than or equal to 24, wherein the etch index is equal to -54.6147+(2.50004)*(Al2O3)+(1.3134)*(B2O3)+(1.84106)*(MgO)+(3.01223)*(CaO)+(3.7248)*(SrO)+(4.13149)*(BaO), wherein Al2O3, B2O3, MgO, CaO, SrO and BaO are expressed in mole percentages.

Citation Information

Patent Citations

  • Sheet forming apparatus

    US3338696A

  • Controlling thickness of newly drawn glass sheet

    US3682609A

  • Method of reducing bubbles at the vessel / glass interface in a glass manufacturing system

    US5785726A

  • Arsenic-free glasses

    US5824127A

  • Arsenic-free glasses

    US6128924A